Decoding BDNF in neurodevelopmental, neurodegenerative, and neurological disorders: mechanisms and therapeutic perspectives - S. P. Raswanthiya; Obert Peterpaul Fernandes; Martin Prince Mathew; Piyush Jagdish Balgote; Jayanthi Sivaraman (Molecular Biology Reports, 2026)

Molecular characterization of extended-spectrum β-lactamases-producing Escherichia coli isolated from patients with bacteremia - Beatrice D. V. L. Souza; Guilherme Solveira; Guilherme F. R. de Souza; Henrique Orsi; Daiany R. P. De Lira; Iranildo do A. Fernandes; Adriano M. Ferreira; Alessandro L. Mondelli; Claudio T. Sacchi; Karoline R. Campos; Marlon B. N. Santos; Carlos H. Camargo; et al. (Brazilian Journal of Microbiology, 2026)
Bacteremia is a major health problem that affects millions of people worldwide. E. coli is one of the main pathogens associated with bacteremia and its resistance to the antimicrobial drugs, including β-lactams, has significantly increased in recent years. In view of the above, our objective was to determine the antimicrobial resistance profile of 60 E. coli isolates obtained from patients with bacteremia, as well as to characterize extended-spectrum β-lactamases (ESBL) -producing isolates. The highest resistance rates were observed for ciprofloxacin (33.3%), levofloxacin (31.7%), cefuroxime (20%) and cefotaxime (20%). Furthermore, 12 isolates (20%) were ESBL producers. Genomic analysis showed that 58.3% of these ESBL-producing isolates belonged to the phylogroup B2, ST131, serotype O25:H4 and carried the following ESBL-encoding genes: bla CTX−M−15 (66.7%), bla CTX−M−8 (16.7%), bla CTX−M−2 (8.7%) or bla CTX−M−27 (8.7%). Our data highlight the high frequency of E. coli ST131 among the ESBL-producing isolates obtained from patients with bacteremia in Botucatu, Brazil.

Total plasma N-glycomic patterns of COVID-19 disease - Georgia Elgood-Hunt; Jack Cheeseman; Richard A. Gardner; Thomas Sénard; Paulina A. Urbanowicz; Alejandro A. Garcia Leon; Cormac McCarthy; Marco P. Monopoli; Daryl L. Fernandes; Craig P. Thompson; Oleg A. Mayboroda; Patrick. W.G. Mallon; et al. (Glycoconjugate Journal, 2026)
Total plasma N -glycans alter in disease states, with few studies focused on COVID-19. A discovery cohort of 310 COVID-19 patients, replicated with 97 COVID-19 patients and tested with 100 COVID-19 patients, was used to unearth the N -glycans capable of distinguishing infection, as well as prognosis of intensive care unit (ICU) admission and mortality. All significant bisected glycans were decreased in patients compared to controls, whilst fucosylated tri-antennary glycans and sialylated tetra-antennary glycans were increased in patients. For both those admitted to the ICU and those who died, Peak 61 (A4G4S4F) was elevated in the more severe disease course, while Peak 29 (FA2G2S2) was lowered. Pinpointing specific glycosylation changes has alluded to a potential story of glycoprotein pathways in response to SARS-CoV-2 infection. This study could be further explored through deriving the glycoproteins associated with the glycans of interest and the glycosylation changes experienced on these proteins. Graphical Abstract

Study of Ni-YSZ anode under pure and diluted NH3 conditions towards NO production - Celina Fernandes; Laura I.V. Holz; Francisco J.A. Loureiro; Sergey M. Mikhalev; Fátima Santos; Duncan P. Fagg; Adélio Mendes (Fuel, 2026)

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Terrestrial environmental change across the Permian-Triassic boundary in the Karoo Zambezi Basin, Mozambique: Integrating palynological, sedimentological and carbon isotope evidence - P. Fernandes; Z. Pereira; J.E. Spangenberg; M. Mendes; G. Lopes; R.C.G.S. Jorge; L. Albardeiro; E. Font; T. Adatte; T. Vennemann; J. Marques (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineering meat, engineering risk: microbiological characterization and survival of pathogens in cellulose nanofiber structures for cultivated meat production - Kamila Habowski; Arthur K.R. da Pia; Nicoly E.R. Oliveira; Milena P. Fernandes; Juliano D.S. Albergaria; João Paulo F. Santos; Érika C. Jorge; Luciana O. Andrade; Anderson S. Sant'Ana (Food Control, 2026)

Association of the endosomal TLR4 pathway with dorsolateral prostatic remodeling induced by perinatal phthalate mixture exposure in rats - Vinícius Luís Rocha da Silva Maria; Ana Clara Pacheco de Santana; Patrick Vieira Souza; Vanessa Aguiar Rocha; Matheus Naia Fioretto; Natália Magosso; Mirella Franco Moreira; Maria Clara Betete Da Silva Fonseca; André Mascarenhas Guariento; Sergio Pereira; Ariana Musa Aquino; Letícia P. Bomfim; et al. (Reproductive Toxicology, 2026)

Phylogeography of the endangered ant species Atta robusta Borgmeier, 1939 (Formicidae: Myrmicinae): insights into genetic structure, demographic history, and conservation priorities - D. C. Cardoso; D. E. E. Pinto; T. M. Fernandes-Salomão; M. P. Cristiano (Insectes Sociaux, 2026)
Atta robusta is a narrow endemic leaf-cutting ant restricted to restinga habitats along Brazil’s southeastern coast. Despite its conservation status, little is known about its evolutionary history and genetic structure. Here, we investigate patterns of genetic variation in A. robusta using mitochondrial (COI–IGS–tRNALeu–COII) and nuclear (EF1alpha copy one) DNA markers sampled across its known range. We assess genetic diversity and population structure and infer relationships among haplotypes using Bayesian phylogenetic analysis and haplotype network reconstruction. We detected moderate haplotype diversity (Hd = 0.7789 for mtDNA and phased Hd = 0.6737 for EF1alpha F1), significant but incomplete population differentiation (ΦST up to 0.61), and a weak to moderate pattern of isolation by distance. Bayesian analyses recovered geographically associated haplotypes with shallow genetic divergence, while nuclear marker exhibited low relative to mitochondrial data. The star-like haplotype network is compatible with multiple demographic scenarios, but neutrality tests did not provide evidence for departures from demographic equilibrium. Overall, our results indicate shallow genetic structure and incomplete spatial differentiation across the species range. These findings highlight the importance of preserving remnant restinga habitats and maintaining landscape connectivity to safeguard genetic diversity in A. robusta and other habitat-specialist ants.

Partially melted coarse matrix and silica-rich object bearing Antarctic cosmic spherules - Dafilgo Fernandes; N G Rudraswami; V P Singh (Journal of Earth System Science, 2026)

Occurrence of acrylamide and 4-methylimidazole in roasted and ground coffee and the effect of L-asparaginase treatment of green coffee on their levels - David S. da Costa; Edna J. H. Ramirez; Sara R. de Carvalho; Patrícia A. C. Braga; José O. Fernandes; Sara C. Cunha; Adriana P. A. Bragotto (Food Additives & Contaminants: Part A, 2026)

Valorization of orange and banana peels through Yarrowia lipolytica solid-state and semi-solid fermentation - Liliana P. Araújo; Andreia Fernandes; Isabel Belo; Marlene Lopes (Biocatalysis and Agricultural Biotechnology, 2026)

Oplonia doceana sp. nov. (Acanthaceae), from the Doce River basin: first record of the genus for Brazil and insights into Graptophyllinae generic delimitation - Paulo Minatel Gonella; Cintia Kameyama; Ulisses Gonçalves Fernandes; Carrie A. Kiel; Eduardo P. Fernandez; Guilherme Medeiros Antar (Plant Systematics and Evolution, 2026)

Synthesis, cytotoxicity and in vitro and in silico anthelmintic activity of eugenol and derivatives against Haemonchus contortus - Raphael F. Oliveira; Andreza P. Braga; Matheus L.F. Barbosa; Karin V.M.M. Ferreira; Sara S.S. Cardoso; Francisco F.S. Lopes; Victor B. Fernandes; Selene M. Morais; Bruno C. Cavalcanti; Wesley L.C. Ribeiro; Letícia O. Rocha; Francisco J.M. Pinto; et al. (Veterinary Parasitology, 2026)

A new cetrorelix-based estrogen-free ovarian synchronization protocol for fixed-time artificial insemination in beef cattle - Getúlio M. da Silveira; Marcelo S. Fernandes; Gilson A. Pessoa; Jaswant Singh; Gregg P. Adams; Carlos E.P. Leonardi (Theriogenology, 2026)

Power dynamics in strategic environmental assessment: examining actors' relations in Portuguese urban planning processes - M. Pereira; M. Pereira; M.L. Fernandes; F. Teles; S. Moreno Pires; P. Silva; C. Rodrigues; C. Jalali; A. Polido (Environmental Impact Assessment Review, 2026)

Can large language models implement agent-based models? An ODD-based replication study - Nuno Fachada; Daniel Fernandes; Carlos M. Fernandes; João P. Matos-Carvalho (Ecological Modelling, 2026)

Designing an optimised carbon capture and utilization network for sustainable e-methane production - Gustavo P. Rangel; Frederico S. Coelho; Marcelino L. Fernandes; A. Rita Martinho; Hugo R. Matias; Belmira Neto (Journal of Cleaner Production, 2026)

Geochemical and Sr-Nd isotope constraints on the provenance of Permian deposits from Mozambique's Lower Karoo Zambezi Basin - R.C.G.S. Jorge; P. Fernandes; Z. Pereira; J.F. Santos; G. Lopes; J. Marques (Journal of African Earth Sciences, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Aerobic composting with goat manure to degrade household pharmaceutical waste: a case study using ciprofloxacin - Juana Angélica Felipe Fernandes; Danilo Carvajal; Adriana C. Mera; Andrea P. Loayza; Diego A. G. Yabbur; Juan Matos (Waste Disposal & Sustainable Energy, 2026)

Low Soil Phosphorus Rates Sustain High Potato Yields in High P-Testing Tropical Oxisols while Foliar Application Enhances Uptake but Not Yield - Tassiane S. Calles; Rogério P. Soratto; Jéssica T. S. Pereira; Laura M. Sciencia; Adalton M. Fernandes; Emerson F. C. Souza; Renato Yagi; Patricio Sandaña (Potato Research, 2026)
Potato yield is highly dependent on phosphorus (P) availability. Although high rates of P fertilizers are commonly applied to potatoes even in high P test soils, the efficiency of these practices is questionable. Foliar P fertilization, particularly during the tuber bulking stage, has emerged as a potential complementary strategy. This study aimed to evaluate whether adjusting the conventional P application rate at planting and applying in-season foliar P could optimize potato production. A field experiment was conducted on tropical Oxisols with high P-resin concentrations (74–123 mg P dm −3 ) in three site-years in southeastern Brazil. Treatments included five soil P rates at planting (0, 22, 44, 88, and 177 kg P ha −1 ) combined or not with three foliar P applications (1.3 kg P ha −1 each) during tuber bulking. Even without soil- or foliar-applied P, potatoes grown in these soils exhibited adequate P nutrition and high tuber yields (43.1–54.8 Mg ha −1 ); however, minimum soil P rates still enhanced tuber initiation and yield. Foliar P application increased leaf P concentration, uptake, and recovery efficiency across all planting P rates but did not improve tuber yield or quality. Increasing planting P rates produced modest yield gains (6.5%), with estimated optima at 33 or 53 kg P ha −1 depending on the regression model. Potatoes can still respond to P fertilization even in soils testing high in P, but substantially lower P rates than those traditionally used in commercial production are sufficient to achieve high yields. Foliar P application did not improve tuber yield or quality. Graphical Abstract

Ex vivo validation of osteogenic efficacy in a bioceramic dual drug-delivery system - Miguel A. Rodrigues; Liliana Grenho; Rita Araújo; João P. Borges; Maria H. Fernandes; Pedro S. Gomes; José D. Santos; Maria A. Lopes (Drug Delivery and Translational Research, 2026)

Combined Analysis of Gait Cycle and Imaging Parameters in Patients with Lumbar Disc Herniation: An Exploratory Study - Inês F. Mendes; Rita N. S. Fernandes; André P. G. Castro; Nuno A. R. Cristino (Annals of Biomedical Engineering, 2026)
This exploratory study investigates the association between imaging findings, clinical symptoms and gait parameters in patients with lumbar disc herniation (LDH). To explore this hypothesis, this study aims (1) to study how IVD height and intervertebral angle measurements obtained from MRI compare with those obtained from X-ray imaging; (2) to compare spatiotemporal gait parameters between LDH patients and healthy individuals and (3) to study if gait parameters vary in relation to clinical and imaging-derived measurements in LDH patients. Patients in this study underwent lumbar spine X-ray imaging and MRI, completed the Oswestry Disability Index (ODI) and Numerical Pain Rating Scale (NPRS) and participated in a gait analysis assessment. Measurements of IVD height and intervertebral angle revealed unexpected higher values in X-ray scans when compared to MRI, particularly in anterior IVD height and upper lumbar levels, providing important hints for the analysis of the initial imaging exam (usually X-ray scan). In addition, the analyzed gait parameters were altered in most LDH patients, with reduced walking speed, cadence, stride length and single support time and increased double support time, comparatively to healthy controls. A general tendency was found between intense radicular pain and high disability (NPRS and ODI scores, respectively) – both reflecting the impact of the clinical condition – and significant IVD pathology – evident on imaging – and altered gait parameters. However, some cases showed inconsistencies between clinical symptoms, imaging findings and gait parameters, suggesting that the relationship between the mentioned parameters is not always consistent. These findings underscore the importance of a multidimensional approach in evaluating LDH biomechanics, integrating clinical and gait parameters, while identifying potential discrepancies between imaging modalities for better initial assessment and follow-up.

Nitrite reduction and the use of aromatic herbs with Staphylococcus equorum as replacement strategies in bacon - P. Bernardo; M.J. Fernandes; M.H. Fernandes; M.P. Teixeira; B. Özkan; C.M. Alfaia; L. Patarata; M.J. Fraqueza (Meat Science, 2026)

Population dynamics and infestation intensity of Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae) in sugarcane (Saccharum spp.): Adult monitoring as a decision-support tool in pest management - Éllen R. Carbognin; Cláudia P. Ferreira; Odair A. Fernandes (Crop Protection, 2026)

Prolonged production cycles in commercial laying hens and its bone repercussions - Denise C. Sousa; Ieverton C. C. Silva; Carlos B. V. Rabello; Lilian F. A. Souza; Webert A. Silva; Thaiza H. T. Fernandes; Ana P. M. Tenório; Valdemiro A. S. Júnior; Fabiano S. Costa (Tropical Animal Health and Production, 2026)

Equine oviduct-specific glycoprotein is modulated by hormones and sperm cells - Pedro Pinto-Bravo; Maria Rosa Rebordão; Ana S. Amaral; Anna Szóstek-Mioduchowska; Carina Fernandes; António M. Galvão; Elisabete Silva; Joana Alpoim-Moreira; Rosário P. Roberto da Costa; Dariusz J. Skarzynski; Graça M Ferreira-Dias (Research in Veterinary Science, 2026)

Effects of Thymus citriodorus and Salvia elegans extracts combined with S. equorum on a clean label fermented cured meat sausage - P. Bernardo; M.J. Fernandes; M.H. Fernandes; M.P. Teixeira; M.I. Rouxinol; M. Laranjo; M. Elias; L. Patarata; M.J. Fraqueza (Meat Science, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Ecological networks reveal strong pest suppression complementarity between birds and bats within rice-dominated agroecosystems in West Africa - Patrícia P. Chaves; Vanessa A. Mata; Paula Lopes; Mutaro Camará; Daniel Coimbra; Djunco Dabo; Ricardo F. de Lima; Miguel Lecoq; Gonçalo Fernandes; Patrícia Guedes; Inês Lacerda; Mark Massaad; et al. (Agriculture, Ecosystems & Environment, 2026)

Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Biodegradation analysis of PHBV/PBAT bilayer films produced industrially - Miguel Fernandes; Andreia F. Salvador; Cristiane C. P. Andrade; António A. Vicente (Environmental Science and Pollution Research, 2025)

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Soil property controls on plasticiser, antioxidant and UV absorber additive degradation across a global soil gradient - Michaela K. Reay; Martine Graf; Maddy Murphy; Charlie Monkley; Perrine J. Florent; Benjamin I. Collins; Nguyen Van Hien; Tran Minh Tien; Andreia Neves Fernandes; Tapan Adhikari; Samantha Viljoen; Mona Tolba; et al. (Environmental Science and Pollution Research, 2025)
Additives in agricultural plastics can leach into the surrounding soil during use or improper disposal. Their subsequent degradation rates directly regulate whether they persist and accumulate to levels with ecotoxicological effects or are rendered benign. However, which soil properties primarily regulate the degradation of additives remains unclear (e.g. soil carbon, pH, available nutrients, microbial biomass and community structure). We assessed the degradation of the common plastic additives with different functionalities (DEHP (di(2-ethylhexyl) phthalate; plasticiser), 2-hydroxy-4-n-octyloxybenzophenone (benzophenone-12; BP12; UV stabiliser) and AO168 (tris(2,4-di- tert -butylphenyl) phosphite; antioxidant)) in soils under controlled moisture and temperature conditions over 21 days across contrasting agricultural soils from six countries across a global transect (Australia, Brazil, Egypt, India, Vietnam and the UK). DEHP followed zero-order degradation kinetics, with negligible degradation in soils with low microbial biomass. BP12 degraded fastest via first-order degradation kinetics via ether cleavage and hydroxyl loss. The degradation of DEHP and BP12 was correlated with soil microbial biomass and nitrate concentration. BP12 degradation products detected included benzophenone and benzoic acid. DEHP is degraded via β-oxidation of alkyl groups to dibutyl phthalate and diethyl phthalate and through ester hydrolysis to phthalic acid. AO168 degraded via abiotic oxidation and phosphate ester hydrolysis to 2,4-di- tert -butyl-phenol, and degradation was not well correlated with any measured soil variable. Overall, these results show that the components of additive mixtures leached into soils will degrade at different rates due to varying mechanisms and controls exerted by the soil microbial biomass. Plastic additives have differing potentials to persist in agricultural soils globally, with some likely to accumulate to levels that may impact soil function and pose an ecotoxicological threat to soil biota.

Future at risk? Specialized flagship herbivores threatened by climate change in the Atlantic Rainforest - Juliane M.F. Bellaver; Diego Hoffmann; Matheus S. Lima-Ribeiro; Lucas A. Kaminski; Ana C.V. Pires; Leandra Bordignon; Geraldo W. Fernandes; Helena P. Romanowski (Journal for Nature Conservation, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Evidence of phenolic compounds as modulators of ChREBP and NRF2 in type 2 diabetes: a review of their potential for drug development - Carina Proença; Maria Carolina Lobo; Ana T. Rufino; José Miguel P. Ferreira de Oliveira; Marisa Freitas; Jenifer Trepiana; María P. Portillo; Félix Carvalho; Eduarda Fernandes (Phytochemistry Reviews, 2025)

Aloysia oblanceolata Moldenke essential oil exhibits antinociceptive activity regulated by opioids, serotonergic, and α2-adrenergic receptors, along with low toxicity and anti-inflammatory effects - Paulo Vinicius L. Santos; Verônica Myrna C. Reis; Edgar T. Chaves; Renata Cunha Silva; Luanna de M. P. Fernandes; Patrícia Danielle Lima de Lima; Joyce Kelly R. da Silva; Pedro Iuri C. da Silva; Pablo Luis B. Figueiredo (Inflammopharmacology, 2025)

Influence of dietary inclusion of Spirulina on growth, carcass, and meat traits of naked neck and fully feathered broilers under heat stress - Elisabete A. Fernandes; Catia F. Martins; Joana R. Sales; Daniela F.P. Carvalho; José A.M. Prates; Madalena Lordelo; Miguel P. Mourato; Luisa L. Martins; Anabela Raymundo; André M. de Almeida (Algal Research, 2025)

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

The combined effects of site susceptibility to invasion and fire on population dynamics of the invasive tree Acacia dealbata - Cristina G. Lima; Rita Bastos; João A. Cabral; Paulo Alves; Paulo M. Fernandes; João P. Honrado; Ingolf Kühn; Eva Malta-Pinto; Elizabete Marchante; David M. Richardson; Mário Santos; Peter H. Verburg; et al. (Biological Invasions, 2025)

Obtaining natural and sustainable blue dyes from the fungus Terana coerulea (Lam.) for textile application – The TEXTBLUESTYLE project - Isabel P. Fernandes; Miguel Gonçalves; Hugo Bogalho; Yara Goulart; Sandrina A. Heleno; Ricardo Calhelha (Phytochemistry Letters, 2025)

Effect of slow feeding and hydraulic retention time on algal-bacterial aerobic granular sludge for low-nitrogen pulp mill wastewater treatment - Josivaldo Sátiro; Joana P. Fernandes; Ana P. Mucha; Ana Paula Gomes; Cristina Sousa Coutinho Calheiros; Raúl Muñoz; Rogério Simões; António Albuquerque (Journal of Environmental Chemical Engineering, 2025)

The cytotoxicity of synthetic cathinones on dopaminergic-differentiated SH-SY5Y neuroblastoma cell line: Exploring the role of β-keto metabolic reduction - Rita P. Lopes; Cláudia C. Miranda; Tiago G. Fernandes; Helena Gaspar; Alexandra M.M. Antunes (Food and Chemical Toxicology, 2025)

Impacts of rural and urban sources on a tropical semiarid region (Acaraú River, Ceará, Brazil): sedimentary sterols and endocrine-disrupting compounds as anthropogenic molecular markers - Rivelino M. Cavalcante; Antonio D. S. Pereira; Marcielly F. B. Lima; Pollyana Morais; Elissandra V. Marques; Gabrielle M. Fernandes; Rafael P. Santos; Ronaldo F. Nascimento; Felipe R. Santos; Lucas B. Moreira (Environmental Geochemistry and Health, 2025)

P30-81 High-throughput RNA sequencing (Transcriptomics) combined with multiparametric New Approach Methodologies (NAMs) for cardiotoxicity risk assessment and mechanistic determination - J. Eakins; C. Bruhn; A. Rosell-Hildago; R. Rex; D. Yuezak; M. Fernandes dos Reis; T. Samatov; A. Hackmann; G.R. Aquino; C. Vogeley; N. Sahini; G. Goussarov; et al. (Toxicology Letters, 2025)

P21-07 Identifying multi-organ effects of a low-dose, real-world mixture of 13 pesticides in rats using traditional and targeted sensitive methods - S. Da Silva Fernandes; S. Malomgre; D. Figueiredo; D. Van Dam; S. Adriaensen; L. Niggemeier; P. Pilva; P. Boor; V. Geissen; B. Vervaet (Toxicology Letters, 2025)

Hydrodynamic investigation of a tube-in-tube membrane reactor/contactor module using CFD simulation - Mateus P. Caixeta; Paulo H. Marrocos; Isabel S. Fernandes; Vítor J.P. Vilar; Ricardo J. Santos (Chemical Engineering Journal, 2025)

Towards climate adaptation: a case study of a Coastal City in Portugal - L Aelenei; S Viana; T Simões; F Amorim; S G Simões; J Barbosa; P Justino; H Gonçalves; J Dinis; G Fernandes (Building and Environment, 2025)

A multispecies microcosm to assess the effect of footwear wastes on soil biota: a contribution towards sustainability - Beatriz Fernandes; Verónica Nogueira; Sirine Bouguerra; Cristiano Soares; Fernanda Fidalgo; Joana Machado; Susana M. P. Carvalho; Maria José Ferreira; Vera Pinto; José Rodrigues; Carlos M. Pereira; Ruth Pereira (Environmental Science and Pollution Research, 2025)
Due to the high quantities of solid waste with high concentrations of chromium that the footwear industry produces and its disposal sites, it is vital to understand whether leather residue itself is harmful to the ecosystem. Thus, a microcosm test with multispecies ( Brassica oleracea and Eisenia fetida ) was carried out using an agricultural soil contaminated with two different leather residues (Wet Blue and Finished Leather) from the footwear industry. After the stabilization period, Brassica oleracea seedlings and Eisenia fetida adults were exposed to these treatments. At the end of the experiment, a series of parameters were analysed in the B. oleracea leaves (leaf chlorophyl content, gas exchange measurements and photosynthetic parameters), in the E. fetida organisms (alkaline comet assay and biomarkers such as acetylcholinesterase and lipid peroxidation) and in the soils (total chromium content, enzymes activity and nitrogen mineralization and potential nitrification). In the case of soil’s enzymatic activity, even though some were significantly altered, no negative effects could be attributed to the leather residues. Moreover, the addition of residues to the soil did not significantly affect the plant species; however, the same was not observed for the earthworm E. fetida when in contact with Finished Leather. Overall, Finished Leather residue was the one that caused more effects on the parameters analysed and therefore its disposal should be carefully examined.

Electrical stimulation of table grape berries as new alternative for postharvest Escherichia coli contamination management - Mariana P. Fernandes; Flávio Rodrigues; Vanessa F. Cardoso; Filipe S. Silva; Margarida M. Fernandes (Postharvest Biology and Technology, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Decomposition and nutrient release dynamics of leaf litter from shrub species in evergreen woodlands - Mariana P. Fernandes; M. Paula Simões; Luiz Gazarini; Manuel Madeira (Plant Biosystems, 2025)

Quantification of alcohol content and identification of fraud in traditional cachaças using NIR spectroscopy - Valber Elias de Almeida; José Félix de B. Neto; Taliana Kênia A. Bezerra; Vanessa P. da Silva; Germano Veras; Railson de Oliveira Ramos; David Douglas de Sousa Fernandes (Food Chemistry, 2025)

Removal of recalcitrant organic matter from landfill leachate through anaerobic co-treatment with domestic wastewater followed by coagulation-flocculation-sedimentation - R. B. Galvão; P. L. B. Borth; F. Fernandes; A. L. S. M. Felício; J. A. de França; E. K. Kuroda (International Journal of Environmental Science and Technology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Teflubenzuron effects on springtail life history traits explained from impairment of its lipid metabolism - Diana Ilyaskina; Saúl Fernandes; Matty P. Berg; Marja H. Lamoree; Cornelis A.M. van Gestel; Pim E.G. Leonards (Science of The Total Environment, 2025)

Links between international market trends, agricultural intensification and extreme sedimentation rates in a transboundary South American coastal lagoon - C. Bueno; A.S.P. Ávila; J.M. Durán; L. Perez; C. Rodríguez-Pérez; G. De León; M. Medina-Elizalde; L. del Puerto; H. Inda; R.C.L. Figueira; P.A.L. Ferreira; I. Etchevers; et al. (Science of The Total Environment, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Reprocessed fuels in a PWR SMR based on NuScale - Samuel Fernandes; Lucas Chaves; João P. Cunha Melo; Karytha M.S. Corrêa; Natália Gonçalves; Teresa Barrachina; Rafael Miró; Claubia Pereira (Annals of Nuclear Energy, 2025)

Experimental autoimmune encephalomyelitis pathogenesis alters along animal age: impact of S100B expression - Ana Rita Ribeiro; Raquel Pereira; Catarina Barros; Andreia Barateiro; Ainhoa Alberro; Afonso P. Basto; Luís Graça; Maria Vaz Pinto; Fábio M. F. Santos; Pedro M. P. Gois; Susan E. Howlett; Adelaide Fernandes (Journal of Neuroimmune Pharmacology, 2025)
Multiple Sclerosis (MS) is the leading inflammatory and non-traumatic cause of disability in young adults, with late-onset MS emerging in middle-aged patients often resulting in poorer treatment responses and worse prognoses. The calcium-binding protein S100B is elevated in MS patients, and its targeting has shown promise in reducing disease severity in experimental autoimmune encephalomyelitis (EAE) models. However, most studies on MS pathology have focused on young animal models, leaving a gap in understanding the effects of age and S100B ablation on disease progression throughout the lifespan. This study aimed to characterize EAE in mice of different ages, examining demyelination, inflammation, and immune responses to determine whether S100B ablation could mitigate MS pathogenesis across the lifespan. EAE was induced in six cohorts of C57BL/6 mice: young adults (3 months), older adults (6 months), and middle-aged (12 months), including corresponding S100B knockout (KO) groups, followed for 23 days. Upon sacrifice, spinal cords were assessed via immunohistochemistry and Real-Time qPCR, while splenocytes were analyzed for immune cell characterization. Results indicated a more severe disease course in 12-month-old mice, marked by increased gliosis, inflammation, and impaired microglial phagocytic activity. Notably, S100B absence reduced gliosis and inflammatory markers across all ages, with 12-month-old S100B KO mice showing increased regulatory T cells. These findings highlight the exacerbating role of age and elevated S100B in MS progression, underscoring the importance of identifying age-specific MS markers and therapeutic targets. Graphical Abstract

Salt reduction strategies for dry cured meat products: The use of KCl and microencapsulated spices and aromatic plant extracts - P. Bernardo; M.J. Fernandes; M.H. Fernandes; M.P. Teixeira; C.M. Alfaia; C. Serrano; L. Patarata; M.J. Fraqueza (Meat Science, 2025)

Critical nitrogen dilution curve for estimating nitrogen nutrition index of common beans - Rogério P. Soratto; Patricio Sandaña; Westefann S. Sousa; Adalton M. Fernandes; Ignacio A. Ciampitti (Field Crops Research, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

The role of vegetation on sediment transport in a macrotidal fringe mangrove forest - Vando J.C. Gomes; Fernanda M. Achete; Eduardo Siegle; Pedro P. de Freitas; Wanessa K. Lima e Silva; Danilo C.L. Gardunho; Marcus E.B. Fernandes; Nils E. Asp (Ocean & Coastal Management, 2025)

Influence of ozonized autohemotherapy at acupuncture points on stallion sperm quality - J.C. Ferraz Jacob; P. Junqueira Ferraz; L. Bastos Mello Rosa; H. Siqueira da Costa e Souza; M. Tainá Resende Ribeiro; A.C. Oliveira de Andrade; V. Souza de Freitas; F. Batalha Knackfuss; V.L. Teixeira de Jesus; J.G. Fernandes Joaquim (Journal of Equine Veterinary Science, 2025)

Resistance training protects the hippocampus and precuneus against atrophy and benefits white matter integrity in older adults with mild cognitive impairment - Isadora C. Ribeiro; Camila V. L. Teixeira; Thiago J. R. de Resende; Brunno M. de Campos; Gabriel B. Silva; Marco C. Uchida; Thamires N. C. Magalhães; Luciana R. Pimentel-Silva; Ítalo K. Aventurato; Brenda C. Gonçalves; Marjorie C. R. da Silva; Liara Rizzi; et al. (GeroScience, 2025)

Pulses of life: Wet events in Botucatu Paleodesert evidenced by trace fossils analysis (earliest Cretaceous, Paraná Basin, Brazil) - Bernardo Peixoto; Daniel Sedorko; Gabriel E.B. de Barros; Heitor Francischini; Renato P. Ghilardi; Marcelo A. Fernandes (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mental disorders related to psychosocial factors among delivery workers: results of a web survey in Brazil - Matheus F. dos Santos; Janaína S. de Siqueira; Fernando R. Feijó; Rita de Cássia P. Fernandes (International Archives of Occupational and Environmental Health, 2025)

Knowledge gaps in legume diversity and distribution and prospects for future research - Moabe Ferreira Fernandes; Gwilym P. Lewis; Mohammad Vatanparast; Flávia Fonseca Pezzini; Matilda J. M. Brown; Luciano P. de Queiroz; Domingos Cardoso; R. Toby Pennington (Brazilian Journal of Botany, 2024)
Despite significant advancements in legume (Leguminosae or Fabaceae) taxonomy, biogeography and phylogenetics, substantial knowledge gaps persist, limiting our ability to understand their diversity, evolutionary history and conservation needs. In this study we used a robust taxonomic backbone and information housed in publicly available biodiversity repositories to quantify global knowledge gaps within the legume family, focusing on the completeness of species inventory (Linnean shortfall), geographic coverage (Wallacean shortfall), and evolutionary representation (Darwinian shortfall). Our findings underscore that approximately 11% of legume species are yet to be described, with high concentrations in regions such as Iran, Northwestern China, Western Australia, Cape Provinces, and Northeast Brazil. The assessment of gaps in geographic coverage revealed that around 19.8% of legume species lack any occurrence record in public databases. Additionally, nearly 50% of species had fewer than ten occurrence records, and another 50% had incomplete geographic coverage relative to their known distributions. Significant geographic gaps were identified in Temperate Asia, particularly Iran, Afghanistan, and Turkey. Furthermore, the limited availability of comprehensive DNA sequence data for key markers (ITS, matK , psbA , rbcL , trnL ), with 52.5% of species lacking sequences for these markers, poses challenges for accurate phylogenetic inference, especially for clades from poorly sampled regions like South America and Temperate Asia. Addressing these gaps requires integrative approaches that combine herbarium collection assessments, targeted fieldwork, enhanced data integration across repositories, and advanced phylogenetic techniques. By prioritising these strategies, we can accelerate the pace of species discovery and refine biogeographical and phylogenetic understanding for this ecologically and economically important group of plants.

Understanding the germination and post-germination from the peptidases metabolism in Parkia multijuga Benth.: an Amazonian dominant legume tree species - Larissa R. Chevreuil; Leonardo de A. Calderon; Josiane C. de Carvalho; Diego P. de Souza; Andreia V. Fernandes; Flávia C. Schimpl; Márcio V. Ramos; Wagner L. Araújo; José Francisco de C. Gonçalves (Brazilian Journal of Botany, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Nitrous oxide abatement and valorization in an ammonia-fueled SOFC stack – Nitric oxide and electricity production - Celina Fernandes; Laura I.V. Holz; Francisco J.A. Loureiro; Miguel Duarte; Duncan P. Fagg; Adélio Mendes (Chemical Engineering Journal, 2024)

Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Saulo F. S. Chaves; Luiz A. S. Dias; Rodrigo S. Alves; Filipe M. Ferreira; Maurício S. Araújo; Marcos D. V. Resende; Elizabete K. Takahashi; João E. Souza; Fernando P. Leite; Samuel B. Fernandes; Kaio Olimpio G. Dias (Tree Genetics & Genomes, 2024)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

Biogeographical Districts of the Caatinga Dominion: A Proposal Based on Geomorphology and Endemism - Marcelo Freire Moro; Vivian Oliveira Amorim; Luciano Paganucci de Queiroz; Luis Ricardo Fernandes da Costa; Rubson Pinheiro Maia; Nigel P. Taylor; Daniela C. Zappi (The Botanical Review, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Assembling the Brazilian flora: overview of Leguminosae diversity - Marli Pires Morim; Fabiana Luiza Ranzato Filardi; Ângela Lúcia Bagnatori Sartori; Marcelo Fragomeni Simon; João Ricardo Vieira Iganci; Gwilym P. Lewis; Haroldo Cavalcante de Lima; Eimear Nic Lughadha; Moabe Ferreira Fernandes; Luciano Paganucci de Queiroz; Domingos Cardoso (Brazilian Journal of Botany, 2024)

Comprehensive dynamics of bacterial and fungal diversity throughout concentrated chicken broth processing: Integrating culture-dependent and independent techniques - José T.D. Rodrigues; Larissa P. Margalho; Arthur K.R. Pia; Héctor Sierra; Louise Tavares; Míriam G. Marquezini; Melline Fontes Noronha; Lucélia Cabral; Wilson José Fernandes Lemos Junior; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2024)

Influence of micro-aeration in the production of volatile fatty acids (VFA) from wastewaters with high salinity - M. Salomé Duarte; Ricardo J.C. Fernandes; João Sousa; Carla Pereira; Daniela P. Mesquita; M. Madalena Alves (Fuel, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Occupation of twigs by ants in the leaf litter: is there a relationship between the morphology of the castes and the entrance hole? - N. S. Silva; R. P. S. Almeida; J. Andrade-Silva; T. T. Fernandes; O. G. M. Silva; D. R. Souza-Campana; R. R. Silva; M. S. C. Morini (Insectes Sociaux, 2024)

3D Models as a Source for Neuroanatomy Education: A Stepwise White Matter Dissection Using 3D Images and Photogrammetry Scans - André S. B. Oliveira; João Vitor A. Fernandes; Vera Louise F. A. Figueiredo; Luciano C. P. C. Leonel; Megan M. J. Bauman; Michael J. Link; Maria Peris-Celda (Brain Topography, 2024)

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Construction and demolition waste as a low-cost adsorbent for water treatment: kinetics, isotherm, thermodynamics, and Fenton regeneration - Danilo H. S. Santos; Larissa F. Queiroz; Luiz D. Silva Neto; Keven E. Santos; Denio D. C. S. das Neves; Anamália F. Silva; Eduardo J. S. Fonseca; Daniel P. Fernandes; Lucas Meili (Environmental Science and Pollution Research, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of coconut processing by-product graded feeding on carcass traits and meat quality of lambs - Felipe J.S. Silva; Dorgival M. Lima Júnior; Beatriz D.O. Fernandes; Anaiane P. Souza; Susana P. Alves; Rui J.B. Bessa; Francisco F.R. Carvalho; Ariosvaldo N. Medeiros (Meat Science, 2024)

The function of mangrove transition zones on the population structure and fishery of the mangrove crab Ucides cordatus on the Brazilian Amazon coast - Cleidson P. Gomes; Danilo C. L. Gardunho; Paulo C. C. Virgulino-Júnior; Marcus E. B. Fernandes (Wetlands Ecology and Management, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Climatic niche evolution and speciation modes in the transisthmian Alpheus shrimps (Caridea: Alpheidae) - Douglas Fernandes Rodrigues Alves; Pablo Ariel Martinez; Samara de P. de Barros‐Alves; Ariádine Cristine de Almeida; Marco Aurélio Mendes Elias; Carla Hurt; Kristin M. Hultgren (Journal of Biogeography, 2024)
Aim We studied the niche evolution and diversification modes in transisthmian Alpheus shrimps by examining the interplay between environmental niche divergence and conservatism in allopatric sister species. In a broader perspective, the current study analysed the evolution of climatic niche and the role of the environment in species diversification of Alpheus transisthmian shrimp. Location Atlantic and Eastern‐Pacific oceans. Taxon Alpheus shrimps (Caridea: Alpheidae). Methods We assembled georeferenced occurrences for 33 species of Alpheus (with 24 sister species) from a time‐calibrated molecular phylogeny. We modelled their ecological niches and assessed niche overlap through pairwise comparisons. Additionally, we performed phylogenetic reconstructions of the ancestral environmental niche, for each niche axis. Results Our results demonstrate that thermal tolerances, food availability and hydrodynamic forces were relevant environmental axes in evolutionary processes in transisthmian species of Alpheus . Among the 528 paired comparisons, we found that most niches were divergent, including in 12 clades formed by pairs of sister species (in only two of these clades were the niches fully equivalent). Phylogenetic reconstructions of ancestral niches showed an initial niche conservatism in all axes, with divergences intensifying in the last 12 million years. Main Conclusions We found evidence that confirms the relevance of the environmental changes that occurred in the West Atlantic and East Pacific for niche evolution in transisthmian Alpheus species, as well as for the emergence of some lineages. Our findings provide evidence for different modes of Alpheus species speciation in a period consistent with the closure of the Isthmus of Panama.

P23-20 Towards safer and sustainable MXene production - S.N. Sankar; J. Fernandes; G. Araújo; F. Cerqueira; P. Alpuim; F. Lebre; A. Ribeiro; E. Alfaro-Moreno; E. Placidi; S. Marras; A. Capasso (Toxicology Letters, 2024)

P06-21 Multiparametric in vitro assays combined with high-throughput RNA sequencing for cardiotoxicity risk assessment and mechanistic insight - S. Llewellyn; A. Rosell-Hidalgo; C. Bruhn; K. Headspith; T. Samatov; A. Hackmann; G.R. Aquino; M. Fernandes dos Reis; R. Rex; D. Yuezak; C. Vogeley; N. Sahini; et al. (Toxicology Letters, 2024)

P06-13 Mitoxantrone disrupts brain glutathione defence and the metabolic pathways in CD-1 mice - A.D. Carvalho; A.M. Araújo; A. Reis-Mendes; C. Oliveira Sequeira; S. Azeredo Pereira; P. Guedes de Pinho; F. Carvalho; S.I. Sá; E. Fernandes; V.M. Costa (Toxicology Letters, 2024)

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Critical potassium dilution curve for potato crops - Patricio Sandaña; Rogério P. Soratto; Júlio César de A. Silva; Alfonso Valenzuela; Renan J. Parecido; Adalton M. Fernandes; Ignacio A. Ciampitti (Field Crops Research, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Size at the onset of morphological sexual maturity, sexual size dimorphism and relative growth of Petrolisthes armatus (Decapoda, Porcellanidae) from Northeastern Brazil - Maria Das Graças Ferreira Alcântara; Ana Laura de Alcântara Pontes; Carla Janes Fernandes Alcantara; Allysson P. Pontes Pinheiro; Whandenson M. Nascimento (Invertebrate Reproduction & Development, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Upcycling of industrial footwear waste into nonwoven fibrous structures with thermal and acoustic insulation properties - Diana I. Alves; Óscar Carvalho; Nuno ATC Fernandes; Livia Tavares Cosentino; Adilson C. Paula Junior; Raul Fangueiro; Diana P. Ferreira (Journal of Environmental Management, 2024)

Nitrogen efficiency indices for sustainable sweet potato production in tropical environments - Adalton M. Fernandes; Patricio Sandaña; Rogério P. Soratto; Nathalia P. Ribeiro; Fabricio E. Rodrigues; Ítala T. Guimarães (Field Crops Research, 2024)

Machine learning for faster estimates of groundwater response to artificial aquifer recharge - Valdrich J. Fernandes; Perry G.B. de Louw; Ruud P. Bartholomeus; Coen J. Ritsema (Journal of Hydrology, 2024)

Using low-shear aerated and agitated bioreactor for producing two specific laccases by trametes versicolor cultures induced by 2,5-xylidine: Process development and economic analysis - André J. Fernandes; Vinícius P. Shibukawa; Arnaldo M.R. Prata; Fernando Segato; Julio C. dos Santos; André Ferraz; Adriane M.F. Milagres (Bioresource Technology, 2024)

Influence of process parameters on biomass gasification: A review of experimental studies in entrained flow reactors and droptube furnaces - A.I. Ferreiro; A.F. Ferreira; E.C. Fernandes; P. Coelho (Biomass and Bioenergy, 2024)

A remote sensing assessment of oak forest recovery after postfire restoration - L. F. Lopes; F. S. Dias; P. M. Fernandes; V. Acácio (European Journal of Forest Research, 2024)
Mediterranean Europe is experiencing a rise in severe wildfires, resulting in growing socioeconomic and ecological impacts. Postfire restoration has become a crucial approach to mitigate these impacts and promote ecosystem recovery. However, the ecological effects of such interventions are still not well understood. We employed remote sensing techniques to evaluate the impact of postfire emergency stabilization on the recovery of deciduous oak forests in Portugal. Our study encompassed 3013 sampling points located in areas with and without postfire interventions. We chose the Normalized Difference Vegetation Index (NDVI) as an indicator of oak forest recovery over a four-year period following wildfires that took place in 2016 and 2017. We used a Generalized Additive Mixed Model (GAMM) to assess how NDVI changed over time as a function of postfire restoration, fire characteristics, topography, and postfire drought events. We found that postfire restoration had a significant positive effect on NDVI recovery over time, although this effect was small. Severe drought and fire recurrence up to six fires had a negative effect on the recovery of NDVI. Conversely, severe wetness and either low or high burn severities had a positive effect on recovery. Our study emphasizes the importance of monitoring postfire restoration effects on forest recovery to guide restoration planning and improve forest management in burned areas. This becomes even more relevant under increased wildfire severity predicted for the Mediterranean region interacting with other climate-driven disturbances, which will further negatively affect forest recovery.

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Molecular phylogeny and divergence time of Harpalyce (Leguminosae, Papilionoideae), a lineage with amphitropical diversification in seasonally dry forests and savannas - Wallace M.B. São-Mateus; Moabe Ferreira Fernandes; Luciano Paganucci de Queiroz; José Eduardo Meireles; Jomar Gomes Jardim; Alfonso Delgado-Salinas; Óscar Dorado; Haroldo Cavalcante de Lima; Rosa Rankin Rodríguez; Pedro Alejandro González Gutiérrez; Gwilym P. Lewis; Martin F. Wojciechowski; et al. (Molecular Phylogenetics and Evolution, 2024)

Fire suppression and land-use strategies drive future dynamics of an invasive plant in a fire-prone mountain area under climate change - Cristina G. Lima; João C. Campos; Adrián Regos; João P. Honrado; Paulo M. Fernandes; Teresa R. Freitas; João A. Santos; Joana R. Vicente (Journal of Environmental Management, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Synthesis of chalcone derivatives by Claisen-Schmidt condensation and in vitro analyses of their antiprotozoal activities - Gabriella B. Souza; Tamiris A. C. Santos; Amanda P. S. Silva; André L. B. S Barreiros; Victória Brandão Nardelli; Ingrid B. Siqueira; Silvio S. Dolabella; Emmanoel.V. Costa; Péricles B. Alves; Ricardo Scher; Roberta P. M. Fernandes (Natural Product Research, 2024)

Fabrication and sensing properties of a molecularly imprinted polymer on a photonic PDMS substrate for the optical detection of C-reactive protein - Sara Resende; José Fernandes; Patrícia C. Sousa; Carlos Calaza; Manuela F. Frasco; Paulo P. Freitas; M. Goreti F. Sales (Chemical Engineering Journal, 2024)

Ruminal modulator additive effect of Stryphnodendron rotundifolium bark in feedlot lambs - Cristiane R. Barbosa; Jéssica C. Pantoja; Tatiane Fernandes; Renata A. Chagas; Carla G. Souza; Aylpy R. D. Santos; Joyce P. Alves; Fernando M. Vargas Junior (Tropical Animal Health and Production, 2024)

Deciphering the role of the morphophysiology of germination and leaves morphoanatomy for differentiation of Brazil nut genotypes - Elmer Viana Gonçalves; Josiane Celerino de Carvalho; Pedro Paulo dos Santos; Karen Cristina P. da Costa; Adamir da Rocha N. Júnior; Larissa Carolina Alves; Katharine Duarte Gonçalves; Roberval Monteiro B. de Lima; Andreia Varmes Fernandes; Wagner Luiz Araújo; José Francisco de C. Gonçalves (Brazilian Journal of Botany, 2024)

Concentrations, sources and risks of polycyclic aromatic hydrocarbons in sediments from the Parnaiba Delta basin, Northeast Brazil - Analine D.C. Andrade; Gabrielle M. Fernandes; Davi A. Martins; Rivelino M. Cavalcante; Michel R.B. Chaves; Alexandre A. de Souza; Jeremias P. da S. Filho; Ronaldo F. Nascimento; Sidney G. de Lima (Chemosphere, 2024)

The razor clam Solen marginatus Pulteney, 1799: A new anthropogenic marine introduction in the Azores Archipelago - Nuno V. Álvaro; Livia Sinigaglia; Patrícia Madeira; Ana Hipólito; Carlos S. Melo; Samuel Arruda; João Filipe Fernandes; Lara Baptista; Sérgio P. Ávila (Regional Studies in Marine Science, 2024)

The combination of electrodeposited chromium (III) and PVD as an industrial viable solution for the replacement of electrodeposited chromium (VI) - X.L. Pinheiro; K. Oliveira; J. Santos; A.V. Girão; A.C. Bastos; M. Sousa; D. Baptista; S. Gomes; R. Lobo; P. Oliveira; A. Monteiro; J.P. Teixeira; et al. (Process Safety and Environmental Protection, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Presenteeism and Low Work Performance Among Fruit Farm Workers in Northeast Brazil - Vitória B. Siqueira; Rita de Cássia P. Fernandes; Fernando M. Carvalho (Journal of Agromedicine, 2024)

Seagrass soils sequester up to half the metal emissions of one of the world's largest smelters - A. Lafratta; O. Serrano; P. Masqué; M. Fernandes; S. Gaylard; P.S. Lavery (Marine Pollution Bulletin, 2023)

A combined framework of Biplots and Machine Learning for real-world driving volatility and emissions data interpretation - E. Ferreira; E. Macedo; P. Fernandes; M.C. Coelho (Sustainable Cities and Society, 2023)

Increased bat hunting at polluted streams suggests chemical exposure rather than prey shortage - Maike Huszarik; Alexis P. Roodt; Teagan Wernicke; Fernanda Chávez; Annika Metz; Moritz Link; Eva Lima-Fernandes; Ralf Schulz; Martin H. Entling (Science of The Total Environment, 2023)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Swiss deep drilling campaign 2019–2022: Geological overview and rock properties with focus on porosity and pore-space architecture - M. Mazurek; T. Gimmi; C. Zwahlen; L. Aschwanden; E.C. Gaucher; M. Kiczka; D. Rufer; P. Wersin; M. Marques Fernandes; M.A. Glaus; L.R. Van Loon; D. Traber; et al. (Applied Geochemistry, 2023)

Mapping socio-environmental pressures to assess Portuguese soil vulnerability - Concha Cano-Díaz; Romy Zeiss; Claudia Carvalho-Santos; Rui P. Carvalho; Sofia R. Costa; A. Carolina Duarte; Paulo Fernandes; Carlos A. Guerra (Applied Geography, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

A novel strategy to predict clonal composites by jointly modeling spatial variation and genetic competition - Filipe M. Ferreira; Saulo F.S. Chaves; Leonardo L. Bhering; Rodrigo S. Alves; Elizabete K. Takahashi; João E. Sousa; Marcos D.V. Resende; Fernando P. Leite; Salvador A. Gezan; José M.S. Viana; Samuel B. Fernandes; Kaio O.G. Dias (Forest Ecology and Management, 2023)

Fermentative parameters and chemical composition of mixed silages from corn-crotalaria intercropping - Carolina M. Costa Araujo; Edgar S. Jara Galeano; Marco A.P. Orrico Junior; Tatiane Fernandes; Joyce P. Alves; Marciana Retore; Mabio S.J. Silva; Ana C.A. Orrico; Rodrigo A. Garcia; Luis A.Z. Machado (Animal Feed Science and Technology, 2023)

The REMAINS R-package: Paving the way for fire-landscape modeling and management - Silvana Pais; Núria Aquilué; Lluís Brotons; João P. Honrado; Paulo M. Fernandes; Adrián Regos (Environmental Modelling & Software, 2023)

LP-26: Pathomics quantifies histmorphological changes in long-term toxin-exposed rat kidneys - S. da Silva Fernandes; G. Schreurs; P. Pilva; P. Boor; B. Vervaet (Toxicology Letters, 2023)

P21-25: Targeting iron dysregulation and oxidative stress for the development of innovative therapeutics against neurodegeneration - R. Oliveira; A.R. Alfenim; P. Soares; F. Borges; F. Remião; C. Fernandes; R. Silva (Toxicology Letters, 2023)

Photoluminescent alginate-based composite inks for anti-counterfeiting security and soft actuator applications - B.D.D. Cruz; D.M. Correia; R. Polícia; N. Pereira; P. Nunes; M. Fernandes; C.R. Tubio; G. Botelho; S. Lanceros-Méndez; V. de Zea-Bermudez (Chemical Engineering Journal, 2023)

The E3 Ubiquitin Ligase SCF Cyclin F Promotes Sequestosome-1/p62 Insolubility and Foci Formation and is Dysregulated in ALS and FTD Pathogenesis - Jennilee M. Davidson; Sharlynn S. L. Wu; Stephanie L. Rayner; Flora Cheng; Kimberley Duncan; Carlo Russo; Michelle Newbery; Kunjie Ding; Natalie M. Scherer; Rachelle Balez; Alberto García-Redondo; Alberto Rábano; et al. (Molecular Neurobiology, 2023)
Amyotrophic lateral sclerosis (ALS)- and frontotemporal dementia (FTD)-linked mutations in CCNF have been shown to cause dysregulation to protein homeostasis. CCNF encodes for cyclin F, which is part of the cyclin F-E3 ligase complex SCF cyclinF known to ubiquitylate substrates for proteasomal degradation. In this study, we identified a function of cyclin F to regulate substrate solubility and show how cyclin F mechanistically underlies ALS and FTD disease pathogenesis. We demonstrated that ALS and FTD-associated protein sequestosome-1/p62 (p62) was a canonical substrate of cyclin F which was ubiquitylated by the SCF cyclinF complex. We found that SCF cyclin F ubiquitylated p62 at lysine(K)281, and that K281 regulated the propensity of p62 to aggregate. Further, cyclin F expression promoted the aggregation of p62 into the insoluble fraction, which corresponded to an increased number of p62 foci. Notably, ALS and FTD-linked mutant cyclin F p.S621G aberrantly ubiquitylated p62, dysregulated p62 solubility in neuronal-like cells, patient-derived fibroblasts and induced pluripotent stem cells and dysregulated p62 foci formation. Consistently, motor neurons from patient spinal cord tissue exhibited increased p62 ubiquitylation. We suggest that the p.S621G mutation impairs the functions of cyclin F to promote p62 foci formation and shift p62 into the insoluble fraction, which may be associated to aberrant mutant cyclin F-mediated ubiquitylation of p62. Given that p62 dysregulation is common across the ALS and FTD spectrum, our study provides insights into p62 regulation and demonstrates that ALS and FTD-linked cyclin F mutant p.S621G can drive p62 pathogenesis associated with ALS and FTD.

Vitamin B12 bioaccumulation in Chlorella vulgaris grown on food waste-derived anaerobic digestate - Konstantinos P. Papadopoulos; Marcella Fernandes de Souza; Lorraine Archer; Ana Camila Zenteno Illanes; Ellen L. Harrison; Fiona Taylor; Matthew P. Davey; Daniela Ahuatzin Gallardo; Allan J. Komakech; Shahla Radmehr; Andre Holzer; Erik Meers; et al. (Algal Research, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Soil and leaf phosphorus thresholds for modern potato production systems in tropical Oxisols - Rogério P. Soratto; Patricio Sandaña; Adalton M. Fernandes; Tassiane S. Calles; Renato Yagi; Emerson F.C. Souza; André L.G. Job; Jéssyca D.L. Martins (European Journal of Agronomy, 2023)

Using deep learning for pruning region detection and plant organ segmentation in dormant spur-pruned grapevines - P. Guadagna; M. Fernandes; F. Chen; A. Santamaria; T. Teng; T. Frioni; D. G. Caldwell; S. Poni; C. Semini; M. Gatti (Precision Agriculture, 2023)
Even though mechanization has dramatically decreased labor requirements, vineyard management costs are still affected by selective operations such as winter pruning. Robotic solutions are becoming more common in agriculture, however, few studies have focused on grapevines. This work aims at fine-tuning and testing two different deep neural networks for: (i) detecting pruning regions (PRs), and (ii) performing organ segmentation of spur-pruned dormant grapevines. The Faster R-CNN network was fine-tuned using 1215 RGB images collected in different vineyards and annotated through bounding boxes. The network was tested on 232 RGB images, PRs were categorized by wood type (W), orientation (Or) and visibility (V), and performance metrics were calculated. PR detection was dramatically affected by visibility. Highest detection was associated with visible intermediate complex spurs in Merlot (0.97), while most represented coplanar simple spurs allowed a 74% detection rate. The Mask R-CNN network was trained for grapevine organs (GOs) segmentation by using 119 RGB images annotated by distinguishing 5 classes (cordon, arm, spur, cane and node). The network was tested on 60 RGB images of light pruned (LP), shoot-thinned (ST) and unthinned control (C) grapevines. Nodes were the best segmented GOs (0.88) and general recall was higher for ST (0.85) compared to C (0.80) confirming the role of canopy management in improving performances of hi-tech solutions based on artificial intelligence. The two fine-tuned and tested networks are part of a larger control framework that is under development for autonomous winter pruning of grapevines.

Collecting young nests of Atta spp. is more efficient to establish laboratory colonies than collecting founder queens after nuptial flights - Tássia T M Santos; Marcus V Santana; Gabriel M Mascarin; Steven P Arthurs; Paulo M Fernandes (International Journal of Tropical Insect Science, 2023)

Assessment of an urban waste disposal contamination using chemical analysis and DC resistivity - W. F. de Borba; J. L. S. da Silva; P. D. da Cunha Kemerich; M. Fries; G. D’. Fernandes; É. E. B. de Souza; L. M. Ilha; G. S. N. da Silva (International Journal of Environmental Science and Technology, 2023)

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Comparison of Apgar score and neonatal parameters between ET and ICSI foals - Juliana S Fonte; Francieli P Carneiro; Barbara K Costa; Maria Augusta Alonso; Perla DC Fleury; Marc P Maserati; Claudia B Fernandes (Journal of Equine Veterinary Science, 2023)

Aquatic environmental DNA: A review of the macro-organismal biomonitoring revolution - Miwa Takahashi; Mattia Saccò; Joshua H. Kestel; Georgia Nester; Matthew A. Campbell; Mieke van der Heyde; Matthew J. Heydenrych; David J. Juszkiewicz; Paul Nevill; Kathryn L. Dawkins; Cindy Bessey; Kristen Fernandes; et al. (Science of The Total Environment, 2023)

TRPV1 inactivation alters core body temperature and serum corticosterone levels: Impacts on clock genes expression in the liver and adrenal glands - Nayara AC. Horta; Paola Fernandes; Thais SR. Cardoso; Frederico SM. Machado; Lucas R. Drummond; Cândido C. Coimbra; Samuel P. Wanner; Ana Maria L Castrucci; Maristela O. Poletini (Journal of Thermal Biology, 2023)

Conjugated linoleic acid trans-10, cis-12 increases the expression of genes from cell cycle progression and cis-9, trans-11 stimulates apoptotic genes in different mammary tumor explants of female dogs - E. D. Da Silva; E. C. Sandri; L. A. Fernandes; P. C. Carraro; D. E. De Oliveira (Molecular Biology Reports, 2023)

Unveiling the membrane bound dihydroorotate: Quinone oxidoreductase from Staphylococcus aureus - Filipe M. Sousa; Patrícia Pires; Andreia Barreto; Patrícia N. Refojo; Micael S. Silva; Pedro B. Fernandes; Ana P. Carapeto; Tiago T. Robalo; Mário S. Rodrigues; Mariana G. Pinho; Eurico J. Cabrita; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

No-tillage and previous maize–palisadegrass intercropping reduce soil and water losses without decreasing root yield and quality of cassava - Francisca G.S. Garreto; Adalton M. Fernandes; Jessica A. Silva; Rudieli M. Silva; Ricardo T. Figueiredo; Rogério P. Soratto (Soil and Tillage Research, 2023)

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Infections by entomopathogenic fungi in common green iguanas (Iguana iguana) in captivity in Brazil - Eduardo Ferreira-Machado; Pedro E Navas-Suárez; Ticiana B Ervedosa; Ketlyn B Figueiredo; Ana C S R de Carvalho; Juliana P F Takahashi; Lidia M Kimura; Leonardo J T de Araújo; Natália C C de Azevedo Fernandes; Thaís C Sanches; Luana Rivas; Mayra Frediani; et al. (Journal of Comparative Pathology, 2023)

Disparate biomes within the Caatinga region are not part of the same evolutionary community: A reply to Araujo et al. (2022) - Rafael Dantas Lima; Moabe F. Fernandes; Marcelo Ferreira de Vasconcelos; Domingos Cardoso; Luciano P. de Queiroz (Journal of Arid Environments, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Global invasibility potential of the shrub Baccharis drancunculifolia - Ulises Olivares-Pinto; Newton P. U. Barbosa; Geraldo Wilson Fernandes (Brazilian Journal of Botany, 2022)

Deep capillary impact of a psyllid gall on its host ecophysiology, architecture and performance - G. Wilson Fernandes; Renata A. Maia; Lucas Arantes-Garcia; Eduardo G. Pereira; Yumi Oki; Marcel G. C. França; Lêda N. P. Costa; Milton Barbosa (Trees, 2022)

Reserve mobilization and the role of primary metabolites during the germination and initial seedling growth of rubber tree genotypes - Josiane C. de Carvalho; José Francisco de Carvalho Gonçalves; Andreia V. Fernandes; Karen C. P. da Costa; Eduardo Euclydes de Lima e Borges; Wagner L. Araújo; Adriano Nunes-Nesi; Márcio V. Ramos; Bala Rathinasabapathi (Acta Physiologiae Plantarum, 2022)

Thanatology in the northern muriqui (Brachyteles hypoxanthus) - Robério Freire Filho; Igor Inforzato; Fernanda P. Tabacow; Waldney Martins; Carla B. Possamai; Daniel Ferraz; Robson O. E. Hack; Samantha Rocha; Daniel V. Slomp; Marcello S. Nery; Letícia Almeida; Naíla Fernandes; et al. (Primates, 2022)

Antarctic Strain of Rhodotorula mucilaginosa UFMGCB 18,377 Attenuates Mucositis Induced by 5-Fluorouracil in Mice - Joana O. P. A. Coutinho; Mônica F. Quintanilha; Marina R. A. Campos; Enio Ferreira; Graciéle C. A. de Menezes; Luiz H. Rosa; Carlos A. Rosa; Katia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; Jacques R. Nicoli; Fabiana C. P. Tiago; et al. (Probiotics and Antimicrobial Proteins, 2022)

Optimization of Leaf Nitrogen Concentration and Monitoring Time for Sustainable Potato Production in Tropics - Fabiana M. Fernandes; Rogério P. Soratto; Patricio Sandaña; Emerson F. C. Souza; Renato Yagi (Journal of Soil Science and Plant Nutrition, 2022)

Geochemistry of sediments in contact with oxygen minimum zone of the eastern Arabian Sea: Proxy for palaeo-studies - Pratima M Kessarkar; Lina L Fernandes; G Parthiban; Siby Kurian; Damodar M Shenoy; J N Pattan; V P Rao; S W A Naqvi; Swati Verma (Journal of Earth System Science, 2022)

A tubular ceramic membrane coated with TiO2-P25 for radial addition of H2O2 towards AMX removal from synthetic solutions and secondary urban wastewater - Alexandre Diório; Jennyfer Díaz-Angulo; Reynel M. Castellanos; Ana I. Gomes; Rosângela Bergamasco; Marcelo Fernandes Vieira; Márcia Dezotti; Miguel Angel Mueses; Fiderman Machuca-Martinez; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2022)

Population genomics of introduced Nile tilapia Oreochromis niloticus (Linnaeus, 1758) in the Democratic Republic of the Congo: Repeated introductions since colonial times with multiple sources - Mare Geraerts; Carl Vangestel; Tom Artois; Jorge Manuel de Oliveira Fernandes; Michiel W. P. Jorissen; Auguste Chocha Manda; Célestin Danadu Mizani; Karen Smeets; Jos Snoeks; Gontran Sonet; Yang Tingbao; Maarten Van Steenberge; et al. (Molecular Ecology, 2022)
During colonial times, Nile tilapia Oreochromis niloticus (Linnaeus, 1758) was introduced into non‐native parts of the Congo Basin (Democratic Republic of the Congo, DRC) for the first time. Currently, it is the most farmed cichlid in the DRC, and is present throughout the Congo Basin. Although Nile tilapia has been reported as an invasive species, documentation of historical introductions into this basin and its consequences are scant. Here, we study the genetic consequences of these introductions by genotyping 213 Nile tilapia from native and introduced regions, focusing on the Congo Basin. Additionally, 48 specimens from 16 other tilapia species were included to test for hybridization. Using RAD sequencing (27,611 single nucleotide polymorphisms), we discovered genetic admixture with other tilapia species in several morphologically identified Nile tilapia from the Congo Basin, reflecting their ability to interbreed and the potential threat they pose to the genetic integrity of native tilapias. Nile tilapia populations from the Upper Congo and those from the Middle–Lower Congo are strongly differentiated. The former show genetic similarity to Nile tilapia from the White Nile, while specimens from the Benue Basin and Lake Kariba are similar to Nile tilapia from the Middle–Lower Congo, suggesting independent introductions using different sources. We conclude that the presence of Nile tilapia in the Congo Basin results from independent introductions, reflecting the dynamic aquaculture history, and that their introduction probably leads to genetic interactions with native tilapias, which could lower their fitness. We therefore urge avoiding further introductions of Nile tilapia in non‐native regions and to use native tilapias in future aquaculture efforts.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

First report of Brenneria goodwinii causing acute oak decline on Quercus suber in Portugal - C. Fernandes; L. Duarte; P. Naves; E. Sousa; L. Cruz (Journal of Plant Pathology, 2022)

Brewer’s Spent Dry Yeast Modulates Immunity in Gilthead Sea Bream (Sparus aurata) - Ioannis Konstantinidis; Joana P. Firmino; Alberto Ruiz; Bruno Iñarra; David San Martin; Alicia Estévez; Jorge M. O. Fernandes; Enric Gisbert (Frontiers in Marine Science, 2022)
In this study, we evaluated the replacement of dietary protein sources like fishmeal (FM) and plant proteins (PP) by Brewer’s spent dry yeast (SDY) on the transcriptomic response (RNA-seq, NextSeq500 platform Illumina) in the liver, anterior-mid intestine, and head kidney in juveniles of gilthead sea bream ( Sparus aurata ). The inclusion of SDY at 30% in the experimental diet (40% crude protein, 16% crude lipid) resulted in a reduction in FM (10%) and PP (31.4%) contents. Using RNA-seq, a total of 19.4 million raw reads per library were obtained, from whose 99.8% of the sequenced data were retained. The alignment efficiency of uniquely mapped reads was 90.3, 89.5, and 89.8% for head kidney, liver, and anterior-mid intestine, respectively. In total, 218 differentially expressed genes (DEGs) were identified among all tissues, out of which, 141 were up- and 77 down-regluated. The enrichment analysis of DEGs revealed that SDY had a modulatory effect on several processes related to host’s immunity, oxygen’s carrier capacity, steroidogenesis, metabolism, and digestion. It is of special relevance the immunomodulatory effects of the tested ingredient as data from RNA-seq showed from the three target tissues analyzed. These results indicated that this ingredient in addition to being considered as a sustainable raw material for replacing conventional protein sources in aquafeeds may also be considered as a functional ingredient due to its content in β-glucans. The overall results of this study coupled with previous nutritional studies on this ingredient indicated the suitability of brewery’s by-products like SDY in aquafeeds for carnivorous species like gilthead seabream, as well as supporting a circular bioeconomy model that reuses, recovers, and recycles resources instead of producing wastes.

Identification of Glycycometus malaysiensis (for the first time in Brazil), Blomia tropicalis and Dermatophagoides pteronyssinus through multiplex PCR - Vítor S. Alves; Luis F. Salazar-Garcés; Leonardo F. Santiago; Paula L. C. Fonseca; Antônio M. S. Fernandes; Raphael C. Silva; Lorena M. Souza; Pedro P. R. S. Cunha; Marina F. C. Barbosa; Eric R. G. R. Aguiar; Luis G. C. Pacheco; Neuza M. Alcantara-Neves; et al. (Experimental and Applied Acarology, 2022)

Metabolomic Signatures of In Vitro Biofilm Maturation of Streptococcus mutans - Aline S. Letieri; Liana B. Freitas-Fernandes; Ivete P. R. Souza; Ana P. Valente; Tatiana K. S. Fidalgo (Current Microbiology, 2022)

Higher frequency of legitimate pollinators and fruit set of autotetraploid trees of Libidibia ferrea (Leguminosae) compared to diploids in a mixed tropical urban population - Willams Oliveira; Jéssica Luiza S. Silva; Oswaldo Cruz-Neto; Marcela Tomaz P. Oliveira; Isabelle Fernandes de Albuquerque; Laís Angélica Borges; Ariadna Valentina Lopes (Journal of Plant Research, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

History and Current Status of Sugarcane Breeding, Germplasm Development and Molecular Genetics in Brazil - D. E. Cursi; H. P. Hoffmann; G. V. S. Barbosa; J. A. Bressiani; R. Gazaffi; R. G. Chapola; A. R. Fernandes Junior; T. W. A. Balsalobre; C. A. Diniz; J. M. Santos; M. S. Carneiro (Sugar Tech, 2022)
Brazil is the world’s largest producer of sugarcane and one of the leading suppliers of sugar and ethanol worldwide. In the 2019–2020 crop season, the country produced 642.7 million tons of sugarcane in a harvest area of 8.44 million hectares. Historically, sugarcane breeding has contributed continuously to increasing yields by regularly releasing superior cultivars for use by the Brazilian industry. In the last 40 years, an average annual increase of 155.7 kg ha −1 of sugar yield has been reported, about half of which may be attributed to breeding programs. However, due to the size of the country, the intensive expansion of the crop to low-fertility soils in the last few years, especially in degraded pasture areas, and the widespread adoption of mechanization, new challenges have been imposed on national breeding programs. This review covers the current situation with sugarcane breeding in Brazil and the main advances that have allowed the country to maintain world leadership in developing the industry. Additionally, the history of sugarcane breeding, current national breeding institutions, germplasm development, key breeding objectives, selection stages and methodologies are summarized. An overview is also presented of biotechnological approaches which have become key tools for improving Brazilian traditional breeding programs. The adoption of strategies to increase Brazilian sugarcane yield, aiming to consolidate crop production in a food and energy matrix, is also discussed.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Effect of pyrolysis temperature on eucalyptus wood residues biochar on availability and transport of hexazinone in soil - B. C. C. Fernandes; K. F. Mendes; V. L. Tornisielo; T. M. S. Teófilo; V. Takeshita; P. S. F. das Chagas; H. A. Lins; M. F. Souza; D. V. Silva (International Journal of Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The ghost vampire: spatio-temporal distribution and conservation status of the largest bat in the Americas - F. Alvarez; S. Gomes da Silva; L. M. Guevara-Chumacero; F. Fernandes Ferreira; L. Alvarez Borla; R. Firmino de Sousa; D. P. Silva (Biodiversity and Conservation, 2021)

The air pollution modelling system URBAIR: how to use a Gaussian model to accomplish high spatial and temporal resolutions - A. P. Fernandes; S. Rafael; D. Lopes; S. Coelho; C. Borrego; M. Lopes (Air Quality, Atmosphere & Health, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Using Predicted Patterns of 3D Prey Distribution to Map King Penguin Foraging Habitat - Roland Proud; Camille Le Guen; Richard B. Sherley; Akiko Kato; Yan Ropert-Coudert; Norman Ratcliffe; Simon Jarman; Adam Wyness; John P. Y. Arnould; Ryan A. Saunders; Paul G. Fernandes; Lars Boehme; et al. (Frontiers in Marine Science, 2021)
King penguins ( Aptenodytes patagonicus ) are an iconic Southern Ocean species, but the prey distributions that underpin their at-sea foraging tracks and diving behaviour remain unclear. We conducted simultaneous acoustic surveys off South Georgia and tracking of king penguins breeding ashore there in Austral summer 2017 to gain insight into habitat use and foraging behaviour. Acoustic surveys revealed ubiquitous deep scattering layers (DSLs; acoustically detected layers of fish and other micronekton that inhabit the mesopelagic zone) at c. 500 m and shallower ephemeral fish schools. Based on DNA extracted from penguin faecal samples, these schools were likely comprised of lanternfish (an important component of king penguin diets), icefish ( Channichthyidae spp.) and painted noties ( Lepidonotothen larseni ). Penguins did not dive as deep as DSLs, but their prey-encounter depth-distributions, as revealed by biologging, overlapped at fine scale (10s of m) with depths of acoustically detected fish schools. We used neural networks to predict local scale (10 km) fish echo intensity and depth distribution at penguin dive locations based on environmental correlates, and developed models of habitat use. Habitat modelling revealed that king penguins preferentially foraged at locations predicted to have shallow and dense (high acoustic energy) fish schools associated with shallow and dense DSLs. These associations could be used to predict the distribution of king penguins from other colonies at South Georgia for which no tracking data are available, and to identify areas of potential ecological significance within the South Georgia and the South Sandwich Islands marine protected area.

Seed germination of six Iberian endemic species – a contribution to enhance plant conservation - Mariana P. Fernandes; Carla Pinto-Cruz; Erika Almeida; Marlene Emídio; M. Paula Simões; Luiz Gazarini; Anabela D. F. Belo (Plant Biosystems, 2021)

Emitters uneveness used in fertigation with biofertilizer - Damiana L. Barros; Eugênio F. Coelho; Tacisio P. de Andrade; Rafael Dreux M. Fernandes; Benedito R. de Oliveira; Lenilson Wisner F. Lima; Mardja Luma da S. Sales (Irrigation Science, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Nicotine gum enhances visual processing in healthy nonsmokers - Thiago P. Fernandes; Natalia L. Almeida; Gabriella M. Silva; Natanael A. Santos (Brain Imaging and Behavior, 2021)

Unlocking the history of a trans‐Atlantic invader: Did the human slave trade impact Brown mussel dispersal? - Sávio H. Calazans; Carla R. Lourenço; Katy R. Nicastro; Claudia H. Tagliaro; Gerardo I. Zardi; Carlos E. L. Ferreira; Flavio da C. Fernandes; Edson P. Silva; Eric A. Hoffman (Journal of Biogeography, 2021)
Aim Brown mussels exhibit a trans‐Atlantic distribution putatively caused by either native dispersal or artificial gene flow, likely in concert with the transport of enslaved people from Africa. Evolutionary history and demographic models of this widespread species may clarify how the present‐day distribution was impacted by natural versus artificial dispersal. Particularly, dating the timing of the South American/African split may determine whether the human slave trade likely impacted the contemporary distribution of brown mussels. Location Coastal Brazil, Morocco, South Africa, and Mozambique. Taxon Perna perna (Linnaeus 1758). Methods We genotyped a total of 644 samples from 18 populations at 10 microsatellite loci. We estimated genetic structure with clustering algorithms in STRUCTURE and GENETIX. We estimated genetic distances by characterizing patterns of pair‐wise F ST using the program FSTAT, evaluating differences among and between regions via AMOVA, and testing isolation by distance in IBDWS. To estimate and date the most likely pathway by which P . perna crossed the Atlantic Ocean we used Bayesian factors from thermodynamically heated coalescent simulations in the program MIGRATE‐n. Results We found no general pattern of reduced or elevated levels of genetic diversity within any region across site or locus. We identified four genetic clusters: East South Africa (ESA), West South Africa (WSA), Brazil (BR) and North Africa (MO); F ST ranged from 0.06 to 0.11 among regions and exhibited a significant pattern of isolation by distance. Migration models indicated that P . perna dispersed from WSA to MO and from there to BR of approximately 2,000 years. Main conclusions Multiple lines of evidence suggest the Brazilian populations of P . perna have been a long‐standing native population, originating from northern Africa and are unlikely a consequence of the African slave trade. Although, human introduction cannot be ruled out South American P . perna populations exhibited genetic characteristics indicative of a divergent, isolated and established population, featuring the genetic signature expected for a native population.

Study of molecular diagnosis and viremia of bluetongue virus in sheep and cattle - Marcela Gasparini; Mateus Laguardia-Nascimento; Érica Bravo Sales; Anna Gabriella Guimarães Oliveira; Zélia I. P. Lobato; Marcelo Fernandes Camargos; Antônio Augusto Fonseca Júnior (Brazilian Journal of Microbiology, 2021)

Twigs in leaf litter: overlap in twig size occupation by nesting ants - R. P. S. Almeida; J. Andrade-Silva; R. R. Silva; T. T. Fernandes; D. R. Souza-Campana; N. S. Silva; M. S. C. Morini (Insectes Sociaux, 2021)

Mannose-conjugated chitosan nanoparticles for delivery of Rifampicin to Osteoarticular tuberculosis - Pratiksha Prabhu; Trinette Fernandes; Pramila Chaubey; Parvinder Kaur; Shridhar Narayanan; Ramya VK; Sujata P. Sawarkar (Drug Delivery and Translational Research, 2021)

How to Meet New Global Targets in the Offshore Realms: Biophysical Guidelines for Offshore Networks of No-Take Marine Protected Areas - Daniela M. Ceccarelli; Kate Davey; Geoffrey P. Jones; Peter T. Harris; Sione V. Matoto; Jason Raubani; Leanne Fernandes (Frontiers in Marine Science, 2021)
Networks of no-take marine protected areas (MPAs), where all extractive activities are prohibited, are the most effective tool to directly protect marine ecosystems from destructive and unsustainable human activities. No-take MPAs and MPA networks have been globally implemented in coastal seas, and their success has been significantly enhanced where science-based biophysical guidelines have informed their design. Increasingly, as human pressure on marine ecosystems is expanding further offshore, governments are establishing offshore MPAs—some very large—or MPA networks. Globally, there are growing calls from scientists, non-government organisations, and national governments to set global conservation targets upwards of 30%. Given that most of the ocean is found either in the high seas or offshore within national Exclusive Economic Zones, large offshore MPAs or networks of MPAs must be a major component of these global targets for ocean protection. However, without adequate design, these offshore MPAs risk being placed to minimise conflict with economic interests, rather than to maximise biodiversity protection. This paper describes detailed biophysical guidelines that managers can use to design effective networks of no-take MPAs in offshore environments. We conducted a systematic review of existing biophysical design guidelines for networks of MPAs in coastal seas, and found consistent elements relating to size, shape, connectivity, timeframes, and representation of biophysical features. However, few of the guidelines are tailored to offshore environments, and few of the large offshore MPAs currently in place were designed systematically. We discuss how the common inshore design guidelines should be revised to be responsive to the characteristics of offshore ecosystems, including giving consideration of issues of scale, data availability, and uncertainty. We propose 10 biophysical guidelines that can be used to systematically design offshore networks of MPAs which will also contribute to the global goal of at least 30% protection globally. Finally, we offer three priority guidelines that reflect the unique conservation needs of offshore ecosystems: emphasising the need for larger MPAs; maximising the inclusion of special features that are known and mapped; and representing minimum percentages of habitats, or, where mapped, bioregions. Ultimately, MPA guidelines need to be embedded within an adaptive management framework, and have the flexibility to respond to emerging knowledge and new challenges.

A placebo-controlled study of the effects of ayahuasca, set and setting on mental health of participants in ayahuasca group retreats - M. V. Uthaug; N. L. Mason; S. W. Toennes; J. T. Reckweg; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; K. van Oorsouw; J. Riba; J. G. Ramaekers (Psychopharmacology, 2021)
Ayahuasca is a plant concoction containing N,N -dimethyltryptamine (DMT) and certain β-carboline alkaloids from South America. Previous research in naturalistic settings has suggested that ingestion of ayahuasca can improve mental health and well-being; however, these studies were not placebo controlled and did not control for the possibility of expectation bias. This naturalistic observational study was designed to assess whether mental health changes were produced by ayahuasca or by set and setting. Assessments were made pre- and post-ayahuasca sessions in 30 experienced participants of ayahuasca retreats hosted in the Netherlands, Spain, and Germany. Participants consumed ayahuasca ( N = 14) or placebo ( N = 16). Analysis revealed a main effect of time on symptoms of depression, anxiety, and stress. Compared to baseline, symptoms reduced in both groups after the ceremony, independent of treatment. There was a main treatment × time interaction on implicit emotional empathy, indicating that ayahuasca increased emotional empathy to negative stimuli. The current findings suggest that improvements in mental health of participants of ayahuasca ceremonies can be driven by non-pharmacological factors that constitute a placebo response but also by pharmacological factors that are related to the use of ayahuasca. These findings stress the importance of placebo-controlled designs in psychedelic research and the need to further explore the contribution of non-pharmacological factors to the psychedelic experience.

Tuber Yield and Quality of Two Potato Cultivars in Response to Nitrogen Fertilizer Management - Natália S. Assunção; Adalton M. Fernandes; Rogério P. Soratto; Lydia Helena S. O. Mota; Nathalia P. Ribeiro; Magali Leonel (Potato Research, 2021)

The first record of the genus Lamellibrachia (Siboglinidae) tubeworm along with associated organisms in a chemosynthetic ecosystem from the Indian Ocean: A report from the Cauvery–Mannar Basin - A Mazumdar; P Dewangan; A Peketi; Firoz Badesaab; Mohd Sadique; Kalyani Sivan; Jittu Mathai; Ankita Ghosh; A Zatale; S P K Pillutla; C Uma; C K Mishra; et al. (Journal of Earth System Science, 2021)

The use of denaturing solution as collection and transport media to improve SARS-CoV-2 RNA detection and reduce infection of laboratory personnel - Alex F. Carvalho; Raissa P. Rocha; Andreza P. Gonçalves; Thaís B. S. Silva; Hugo I. Sato; Larissa Vuitika; Flavia F. Bagno; Sarah A. R. Sérgio; Maria M. Figueiredo; Ronaldo B. Martins; Juliano P. Souza; Eurico Arruda; et al. (Brazilian Journal of Microbiology, 2021)

Water Quality of the Gualaxo do Norte and Carmo Rivers After the Fundão Dam Collapse, Mariana, MG - Felipe C. Santana; Márcio R. Francelino; Carlos E. G. R. Schaefer; Gustavo V. Veloso; Elpídio I. Fernandes-Filho; Adalgisa de J. P. Santana; Lucas B. Timo; André P. Rosa (Water, Air, & Soil Pollution, 2021)

Photocatalytic degradation of acetaminophen and caffeine using magnetite–hematite combined nanoparticles: kinetics and mechanisms - Tiago A. Fernandes; Sofia G. Mendo; Liliana P. Ferreira; Nuno R. Neng; M. Conceição Oliveira; Adrià Gil; Maria Deus Carvalho; Olinda C. Monteiro; José M. F. Nogueira; Maria José Calhorda (Environmental Science and Pollution Research, 2021)

Chemical composition and larvicidal activity of the essential oil from the leaves of Onychopetalum periquino (Rusby) D.M. Johnson & N.A. Murray - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Jessica B. Maciel; Carromberth C. Fernandes; André C. de Oliveira; Wanderli P. Tadei; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2021)

Feed intake, digestibility, and energy contents in growing bull fed pineapple crop waste silage in different planes of nutrition - Bernardo L. B. Mello; Alberto M. Fernandes; Tadeu S. de Oliveira; Fernando P. Leonel; Leonardo S. Glória; Renata S. T. Silva (Tropical Animal Health and Production, 2021)

Effects of additives in wet brewery residue silage on lamb carcass traits and meat quality - Karen S. F. de Abreu; Adriana Guim; Francisco F. F. Carvalho; Marcelo de A. Ferreira; João Paulo I. dos S. Monnerat; João V. C. Fernandes; Ana C. C. P. Lima; Caio C. C. dos Santos; José F. da Silva Neto (Tropical Animal Health and Production, 2021)

Using untapped telemetry data to explore the winter biology of freshwater fish - J. E. Marsden; P. J. Blanchfield; J. L. Brooks; T. Fernandes; A. T. Fisk; M. H. Futia; B. L. Hlina; S. V. Ivanova; T. B. Johnson; N. V. Klinard; C. C. Krueger; S. M. Larocque; et al. (Reviews in Fish Biology and Fisheries, 2021)

An assessment of the MOD17A2 gross primary production product in the Caatinga biome, Brazil - Rosaria R. Ferreira; Pedro Mutti; Keila R. Mendes; Suany Campos; Thiago V. Marques; Cristiano P. Oliveira; Weber Gonçalves; Jonathan Mota; Gelson Difante; Stella A. Urbano; Leonardo Fernandes; Bergson G. Bezerra; et al. (International Journal of Remote Sensing, 2021)

MT1 and MT2 melatonin receptors play opposite roles in brain cancer progression - G. S. Kinker; L. H. Ostrowski; P. A. C. Ribeiro; R. Chanoch; S. M. Muxel; I. Tirosh; G. Spadoni; S. Rivara; V. R. Martins; T. G. Santos; R. P. Markus; P. A. C. M. Fernandes (Journal of Molecular Medicine, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biomass Accumulation and Nutritional Requirements of Potato as Affected by Potassium Supply - Rogério P. Soratto; André L. G. Job; Adalton M. Fernandes; Natália S. Assunção; Fabiana M. Fernandes (Journal of Soil Science and Plant Nutrition, 2020)

Effects of Maternal Dietary Cottonseed on the Profile of Minerals in the Testes of the Lamb - Helder Louvandini; Egon H. Ieda; Carolina R. Jimenez; Patricia Spoto Corrêa; Debora B. Moretti; Paulo M. T. Lima; Concepta M. McManus; Hudson W. P. Carvalho; Elisabete A. De N. Fernandes (Biological Trace Element Research, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Efficacy of Metarhizium anisopliae conidia in oil-in-water emulsion against the tick Rhipicephalus microplus under heat and dry conditions - Elen R. Muniz; Flávia R. S. Paixão; Lucas P. Barreto; Christian Luz; Walquíria Arruda; Isabele C. Angelo; Éverton K. K. Fernandes (BioControl, 2020)

Cohabitation and niche overlap in the occupation of twigs by arthropods in the leaf litter of Brazilian Atlantic Forest - T. T. Fernandes; W. Dáttilo; R. R. Silva; P. Luna; A. B. Braz; M. S. C. Morini (Insectes Sociaux, 2020)

Silver nanoparticle from whole cells of the fungi Trichoderma spp. isolated from Brazilian Amazon - Matheus M. Ramos; Edmilson dos S. Morais; Iracirema da S. Sena; Adilson L. Lima; Fábio R. de Oliveira; Calleu M. de Freitas; Caio P. Fernandes; José Carlos T. de Carvalho; Irlon M. Ferreira (Biotechnology Letters, 2020)

Tannic Acid Ameliorates STZ-Induced Alzheimer’s Disease-Like Impairment of Memory, Neuroinflammation, Neuronal Death and Modulates Akt Expression - Mariana F. B. Gerzson; Natália P. Bona; Mayara S. P. Soares; Fernanda C. Teixeira; Francine L. Rahmeier; Fabiano B. Carvalho; Marilda da Cruz Fernandes; Giovana Onzi; Guido Lenz; Relber A. Gonçales; Roselia M. Spanevello; Francieli M. Stefanello (Neurotoxicity Research, 2020)

Assessing the impact of sulfur concentrations on growth and biochemical composition of three marine microalgae - Tomásia Fernandes; Igor Fernandes; Carlos A. P. Andrade; Nereida Cordeiro (Journal of Applied Phycology, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Inhibitory Effect of 5-Aminoimidazole-4-Carbohydrazonamides Derivatives Against Candida spp. Biofilm on Nanohydroxyapatite Substrate - C. Gabriel; L. Grenho; F. Cerqueira; R. Medeiros; A. M. Dias; A. I. Ribeiro; M. F. Proença; M. H. Fernandes; J. C. Sousa; F. J. Monteiro; M. P. Ferraz (Mycopathologia, 2019)

Investigation of the noise properties at low frequencies in long GNSS time series - X. He; M. S. Bos; J. P. Montillet; R. M. S. Fernandes (Journal of Geodesy, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Distribution and source apportionment of hydrocarbons in sediments of oil-producing continental margin: a fuzzy logic approach - Angela de L. R. Wagener; Ana P. Falcão; Cassia O. Farias; Flávio Fernandes Molina; Renato da Silva Carreira; Cristiane Mauad; Adriana Nudi; Arthur de L. Scofield; Carlos German Massone (Environmental Science and Pollution Research, 2019)

Using internal transcribed spacers for Calanoida (Crustacea, Copepoda) species identification - Gustavo M. Rocha; Arturo B. Martinelli; Laura Roberta P. Utz; Luiz F. Loureiro Fernandes (Marine Biodiversity, 2019)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Application of nitrogen and boron isotopes for tracing sources of anthropogenic contamination in Monforte-Alter do Chão aquifer system, Portugal - P. Fernandes; M. R. Carvalho; M. C. Silva; A. Rebelo; J. Zeferino (Sustainable Water Resources Management, 2019)

Transcriptomics of Arabidopsis sperm cells at single-cell resolution - Chandra Shekhar Misra; Mário R. Santos; Mariana Rafael-Fernandes; Nuno P. Martins; Marta Monteiro; Jörg D. Becker (Plant Reproduction, 2019)

A New Species of the Acanthocephalan Genus Filisoma (Cavisomidae) from Perciform Fishes in Rio de Janeiro, Brasil - Viviane S. Costa Fernandes; Omar Amin; Juliana N. Borges; Cláudia P. Santos (Acta Parasitologica, 2019)

Modulation of reactive oxygen levels and gene expression in sensitive and resistant tumoral cells by C-phyocyanin - E. Fernandes e Silva; F. S. Figueira; A. P. Lettnin; M. T. S. F. Salgado; A. C. Lopes; F. Rehbein; S. J. Kalil; A. P. S. Votto (Molecular Biology Reports, 2019)

Adipocyte proteome and secretome influence inflammatory and hormone pathways in glioma - J. Almeida; J. Costa; P. Coelho; V. Cea; M. Galesio; J. P. Noronha; M. S. Diniz; C. Prudêncio; R. Soares; C. Sala; Rúben Fernandes (Metabolic Brain Disease, 2019)

Incorporation of Collagen from Marine Sponges (Spongin) into Hydroxyapatite Samples: Characterization and In Vitro Biological Evaluation - J. R. Parisi; K. R. Fernandes; I. R. Avanzi; B. P. Dorileo; A. F. Santana; A. L. Andrade; P. R. Gabbai-Armelin; C. A. Fortulan; E. S. Trichês; R. N. Granito; A. C. M. Renno (Marine Biotechnology, 2019)

Sandy Beaches as Biogeochemical Hotspots: The Metabolic Role of Macroalgal Wrack on Low-productive Shores - Iván F. Rodil; Mariano Lastra; Jesús López; Ana P. Mucha; Joana P. Fernandes; Sara V. Fernandes; Celia Olabarria (Ecosystems, 2019)

Profile of pterostilbene-induced redox homeostasis modulation in cardiac myoblasts and heart tissue - G K Couto; R O Fernandes; D Lacerda; C Campos-Carraro; P Türck; S E Bianchi; G D Ferreira; I S Brum; V L Bassani; A Belló-Klein; A S R Araujo (Journal of Biosciences, 2018)

DNA binding, cleavage and cytotoxicity studies of three mononuclear Cu(II) chloro-complexes containing N–S donor Schiff base ligands - Sidhali U. Parsekar; Joseph Fernandes; Arnab Banerjee; Om Prakash Chouhan; Sumit Biswas; Manohar Singh; Durga P. Mishra; Manjuri Kumar (JBIC Journal of Biological Inorganic Chemistry, 2018)

Brachyuran crab (Crustacea, Decapoda) assemblage associated with Sargassum cymosum in southeastern Brazil - Samara de P. Barros-Alves; Douglas Fernandes Rodrigues Alves; Valter José Cobo (Marine Biodiversity, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Morphometric differences between two exotic invasive freshwater caridean species (genus Macrobrachium ) - Thiago Elias da Silva; Douglas Fernandes Rodrigues Alves; Samara de P. Barros-Alves; Ariádine Cristine Almeida; Fabiano Gazzi Taddei; Adilson Fransozo (Invertebrate Reproduction & Development, 2018)

Drug liking and wanting, not impulsive action or reflection is increased by 4-fluoroamphetamine - K. P. C. Kuypers; E. B. de Sousa Fernandes Perna; P. C. Dolder; S. W. Toennes; E. L. Theunissen; N. L. Mason; N. R. P. W. Hutten; J. G. Ramaekers (Psychopharmacology, 2018)

Characterization and Comparison of Genetic Variation in Cotesia flavipes (Hymenoptera: Braconidae) Mass Reared for Biological Pest Control Using Microsatellite Markers - F C Freitas; A C Morales-Corrêa e Castro; N C C P Barbosa; O A Fernandes (Neotropical Entomology, 2018)

The deadly route to collapse and the uncertain fate of Brazilian rupestrian grasslands - G. Wilson Fernandes; N. P. U. Barbosa; B. Alberton; A. Barbieri; R. Dirzo; F. Goulart; T. J. Guerra; L. P. C. Morellato; R. R. C. Solar (Biodiversity and Conservation, 2018)

Getting the Jump on the Development of Bullfrog Oil Microemulsions: a Nanocarrier for Amphotericin B Intended for Antifungal Treatment - Wógenes N. Oliveira; Lucas Amaral-Machado; Everton N. Alencar; Henrique R. Marcelino; Julieta Genre; Walicyranison P. Silva-Rocha; Amanda D. Gondim; Guilherme M. Chaves; Matheus F. Fernandes-Pedrosa; Eryvaldo Socrates T. Egito (AAPS PharmSciTech, 2018)

Can Bradyrhizobium strains inoculation reduce water deficit effects on peanuts? - D. D. Barbosa; S. L. Brito; P. D. Fernandes; P. I. Fernandes-Júnior; L. M. Lima (World Journal of Microbiology and Biotechnology, 2018)

Proteomic identification and purification of seed proteins from native Amazonian species displaying antifungal activity - Márcio V. Ramos; Daniel Brito; Cléverson D. T. Freitas; José Francisco C. Gonçalves; Camila T. M. N. Porfirio; Marina D. P. Lobo; Ana Cristina O. Monteiro-Moreira; Luiz A. C. Souza; Andreia V. Fernandes (Planta, 2018)

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya - Johana Madroñero; Silas P. Rodrigues; Tathiana F. S. Antunes; Paolla M. V. Abreu; José A. Ventura; A. Alberto R. Fernandes; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Climate change alters fish community size‐structure, requiring adaptive policy targets - Ana M Queirós; José Fernandes; Lily Genevier; Christopher P Lynam (Fish and Fisheries, 2018)
Size‐based indicators are used worldwide in research that supports the management of commercially exploited wild fish populations, because of their responsiveness to fishing pressure. Observational and experimental data, however, have highlighted the deeply rooted links between fish size and environmental conditions that can drive additional, interannual changes in these indicators. Here, we have used biogeochemical and mechanistic niche modelling of commercially exploited demersal fish species to project time series to the end of the 21st century for one such indicator, the large fish indicator ( LFI ), under global CO 2 emissions scenarios. Our modelling results, validated against survey data, suggest that the LFI 's previously proposed policy target may be unachievable under future climate change. In turn, our results help to identify what may be achievable policy targets for demersal fish communities experiencing climate change. While fisheries modelling has grown as a science, climate change modelling is seldom used specifically to address policy aims. Studies such as this one can, however, enable a more sustainable exploitation of marine food resources under changes unmanageable by fisheries control. Indeed, such studies can be used to aid resilient policy target setting by taking into account climate‐driven effects on fish community size‐structure.

Intralesional uridine-5′-triphosphate (UTP) treatment induced resistance to Leishmania amazonensis infection by boosting Th1 immune responses and reactive oxygen species production - Camila Marques-da-Silva; Mariana M. Chaves; Maria Luiza Thorstenberg; Vanessa R. Figliuolo; Flávia S. Vieira; Suzana P. Chaves; José Roberto Meyer-Fernandes; Bartira Rossi-Bergmann; Luiz Eduardo Baggio Savio; Robson Coutinho-Silva (Purinergic Signalling, 2018)

17α-Ethinylestradiol and 17β-estradiol removal from a secondary urban wastewater using an RBC treatment system - R. Maurício; R. Dias; V. Ribeiro; S. Fernandes; A. C. Vicente; M. I. Pinto; J. P. Noronha; L. Amaral; P. Coelho; A. P. Mano (Environmental Monitoring and Assessment, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Assessment of the Bioaccessibility of Trace Elements in Cat’s Claw Teas by In Vitro Simulated Gastrointestinal Digestion Using FAAS - João B. Pereira Junior; Robson C. M. Brito; Lana P. B. Pereira; Kelly G. Fernandes Dantas (Biological Trace Element Research, 2018)

Combination of etoposide and fisetin results in anti-cancer efficiency against osteosarcoma cell models - José Miguel P. Ferreira de Oliveira; Ana Rita Pacheco; Laura Coutinho; Helena Oliveira; Sónia Pinho; Luis Almeida; Eduarda Fernandes; Conceição Santos (Archives of Toxicology, 2018)

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

Molecular and experimental evidence of Watermelon (Citrullus lanatus) as host of the Mexican variant of Papaya meleira virus - I. García-Cámara; D. Pérez-Brito; O. Moreno-Valenzuela; A. Magaña-Álvarez; P. M. B. Fernandes; Raul Tapia-Tussell (European Journal of Plant Pathology, 2017)

Advances on the molecular characterization, clinical relevance, and detection methods of Gadiform parvalbumin allergens - Telmo J. R. Fernandes; Joana Costa; Isabel Carrapatoso; Maria Beatriz P. P. Oliveira; Isabel Mafra (Critical Reviews in Food Science and Nutrition, 2017)

Standardization and Prevalence of the Booster Phenomenon: Evaluation Using a Two-Step Skin Test with 43 kDa Glycoprotein in Individuals from an Endemic Region of Paracoccidioidomycosis - Ana Paula C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Rinaldo P. Mendes; Anamaria M. M. Paniago (Mycopathologia, 2017)

Middle-Aged Diabetic Females and Males Present Distinct Susceptibility to Alzheimer Disease-like Pathology - E. Candeias; A. I. Duarte; I. Sebastião; M. A. Fernandes; A. I. Plácido; C. Carvalho; S. Correia; R. X. Santos; R. Seiça; M. S. Santos; C. R. Oliveira; P. I. Moreira (Molecular Neurobiology, 2017)

The mating system of the symbiotic pea-crab Dissodactylus crinitichelis (Brachyura, Pinnotheridae): monogamy or promiscuity? - Douglas Fernandes Rodrigues Alves; Gustavo Luis Hirose; Samara de P. Barros-Alves; J. Antonio Baeza (Marine Biology, 2017)

Hyperthermia Severely Affects the Vascular Effects of MDMA and Metabolites in the Human Internal Mammary Artery In Vitro - D. A. Fonseca; A. F. Guerra; F. Carvalho; E. Fernandes; L. M. Ferreira; P. S. Branco; P. E. Antunes; M. J. Antunes; M. D. Cotrim (Cardiovascular Toxicology, 2017)

A new species of Astyanax (Characiformes: Characidae) from Dolina Água Milagrosa, Rio Paraguai basin, Mato Grosso, Brazil - W. J. da Graça; C. A. M. Oliveira; F. C. T. Lima; H. P. da Silva; I. M. Fernandes (Journal of Fish Biology, 2017)
A new species of Astyanax is described from the upper Rio Paraguai basin, Mato Grosso State, Brazil. The new species can be distinguished from congeners by having the body intensely yellowish in life ( v . silvery, reddish or lightly yellow) and by morphometric and meristics traits. Astyanax dolinae n. sp. cannot be assigned to any of the Astyanax species complex currently recognized for the genus. It is only known from the Dolina Água Milagrosa, a karstic sinkhole lake, entirely fed by groundwater, surrounded by Cerrado, the savannah‐like vegetation of central South America.

Functionalization of Cotton by RGO/TiO2 to Enhance Photodegradation of Rhodamine B Under Simulated Solar Irradiation - S. Landi; J. O. Carneiro; F. Fernandes; P. Parpot; J. Molina; F. Cases; J. Fernández; J. G. Santos; G. M. B. Soares; V. Teixeira; A. P. Samantilleke (Water, Air, & Soil Pollution, 2017)

Turn down the heat: regional climate change impacts on development - Christopher P. O. Reyer; Kanta Kumari Rigaud; Erick Fernandes; William Hare; Olivia Serdeczny; Hans Joachim Schellnhuber (Regional Environmental Change, 2017)

Relatedness and body size influence territorial behaviour in Salmo salar juveniles in the wild - W. P. A. Fernandes; S. W. Griffiths; A. T. Ibbotson; W. D. Riley (Fisheries Management and Ecology, 2017)
Wild Atlantic salmon, Salmo salar L., juveniles defend territories to enable exclusive access to food resources, and kin selection benefits may be accrued where territorial boundaries of relatives overlap. This study explored space sharing events between pairs of sibling and non‐sibling fish as a measure of territoriality and resource competition in a small chalk stream using passive integrated transponder ( PIT ) technology. The time period between fish detections in a shared space was closer between pairs of siblings (sibling pairs mean = 60.48 ± 51.84 min; non‐sibling pairs mean = 348.8 ±65.94 min). These results suggest that the territorial boundaries of related fish often overlap, thus increasing the likelihood of siblings accruing kin selection benefits. The findings from this study also suggest that outcomes of competitive interactions among dominant and subordinate fish are less pronounced when fish are related.

Coupling fire behaviour modelling and stand characteristics to assess and mitigate fire hazard in a maritime pine landscape in Portugal - B. Botequim; P. M. Fernandes; J. Garcia-Gonzalo; A. Silva; J. G. Borges (European Journal of Forest Research, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Low Temperature Storage of Telenomus remus (Nixon) (Hymenoptera: Platygastridae) and its Factitious Host Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) - A P Queiroz; A F Bueno; A POMARI-FERNANDES; M L M Grande; O C Bortolotto; D M Silva (Neotropical Entomology, 2017)

Lethal and growth inhibitory activities of Neotropical Annonaceae-derived extracts, commercial formulation, and an isolated acetogenin against Helicoverpa armigera - Camila M. Souza; Edson L. L. Baldin; Leandro P. Ribeiro; Ivana F. Silva; Rafaela Morando; Keylla U. Bicalho; José D. Vendramim; João B. Fernandes (Journal of Pest Science, 2017)

First Record of Euphoria lurida Fabricius (Coleoptera: Scarabaeidae) Injurious to Safflower (Carthamus tinctorius L.) (Asterales: Asteraceae) in Brazil - H G Androcioli; A T Hoshino; M A Pastório; P C Cardoso; P M de Araújo; T A P Fernandes; A O Menezes (Neotropical Entomology, 2017)

The Cost of Reducing the North Atlantic Ocean Biological Carbon Pump - Manuel Barange; Momme Butenschön; Andrew Yool; Nicola Beaumont; Jose A. Fernandes; Adrian P. Martin; J. Icarus Allen (Frontiers in Marine Science, 2017)

The pigments of kelps (Ochrophyta) as part of the flexible response to highly variable marine environments - Fátima Fernandes; Mariana Barbosa; Andreia P. Oliveira; Isabel C. Azevedo; Isabel Sousa-Pinto; Patrícia Valentão; Paula B. Andrade (Journal of Applied Phycology, 2016)

Assessing the conservation status of Mediterranean temporary ponds using biodiversity: a new tool for practitioners - A. Lumbreras; J. T. Marques; A. F. Belo; M. Cristo; M. Fernandes; D. Galioto; M. Machado; A. Mira; P. Sá-Sousa; R. Silva; L. G. Sousa; C. Pinto-Cruz (Hydrobiologia, 2016)

Subjective aggression during alcohol and cannabis intoxication before and after aggression exposure - E. B. De Sousa Fernandes Perna; E. L. Theunissen; K. P. C. Kuypers; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2016)

Response of Potato Cultivars to Phosphate Fertilization in Tropical Soils with Different Phosphorus Availabilities - Adalton M. Fernandes; Rogério P. Soratto (Potato Research, 2016)

Combined Effect of Heat Shock and Chlorine Fails to Elicit Acquired Thermal Tolerance in Labeo rohita Spawns - Jolyn Fernandes; A. K. Pal; Prem Kumar; P. P. Chandrachoodan; M. S. Akhtar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Phosphorus Fertilizer Rate for Fresh Market Potato Cultivars Grown in Tropical Soil with Low Phosphorus Availability - Adalton M. Fernandes; Rogério P. Soratto (American Journal of Potato Research, 2016)

Air quality plan for ozone: an urgent need for North Portugal - C. Borrego; A. Monteiro; H. Martins; J. Ferreira; A. P. Fernandes; S. Rafael; A. I. Miranda; M. Guevara; J. M. Baldasano (Air Quality, Atmosphere & Health, 2016)

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

Amblyomin-X induces ER stress, mitochondrial dysfunction, and caspase activation in human melanoma and pancreatic tumor cell - Katia L. P. Morais; Mario Thiego Fernandes Pacheco; Carolina Maria Berra; Rosemary V. Bosch; Juliana Mozer Sciani; Roger Chammas; Renata de Freitas Saito; Asif Iqbal; Ana Marisa Chudzinski-Tavassi (Molecular and Cellular Biochemistry, 2016)

Evaluation of resistance in different cowpea cultivars to Callosobruchus maculatus infestation - Luana P. Cruz; Leonardo F. R. de Sá; Layrana A. Santos; Geraldo A. Gravina; André O. Carvalho; Kátia Valevski S. Fernandes; Francisco R. Freire Filho; Valdirene M. Gomes; Antonia Elenir A. Oliveira (Journal of Pest Science, 2016)

Leaf Fluctuating Asymmetry and Herbivory of Tibouchina heteromalla in Restored and Natural Environments - G W Fernandes; S C S de Oliveira; I R Campos; M Barbosa; L A Soares; P Cuevas-Reyes (Neotropical Entomology, 2016)

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction - Alexandre Luz de Castro; Rafael Oliveira Fernandes; Vanessa D. Ortiz; Cristina Campos; Jéssica H. P. Bonetto; Tânia R. G. Fernandes; Adriana Conzatti; Rafaela Siqueira; Angela Vicente Tavares; Paulo Cavalheiro Schenkel; Adriane Belló-Klein; Alex Sander da Rosa Araujo (Apoptosis, 2016)

Assessment of environment, land management, and spatial variables on recent changes in montado land cover in southern Portugal - Sérgio Godinho; Nuno Guiomar; Rui Machado; Pedro Santos; Paulo Sá-Sousa; J. P. Fernandes; Nuno Neves; Teresa Pinto-Correia (Agroforestry Systems, 2016)

Relationship of Sediment-Biochemistry, Bacterial Morphology, and Activity to Geotechnical Properties in the Central Indian Basin - Sonali Shyam Naik; N. H. Khadge; A. B. Valsangkar; Anindita Das; Christabelle E. G. Fernandes; P. A. Loka Bharathi (Marine Georesources & Geotechnology, 2016)

Acetyl-L-Carnitine Prevents Methamphetamine-Induced Structural Damage on Endothelial Cells via ILK-Related MMP-9 Activity - S. Fernandes; S. Salta; J. Bravo; A. P. Silva; T. Summavielle (Molecular Neurobiology, 2016)

Contributions of hydrogeophysics to the hydrogeological conceptual model of the Albufeira-Ribeira de Quarteira coastal aquifer in Algarve, Portugal - Alain P. Francés; Elsa C. Ramalho; Judite Fernandes; Michel Groen; Rui Hugman; Mohamed A. Khalil; Joel De Plaen; Fernando A. Monteiro Santos (Hydrogeology Journal, 2015)

Selectivity of Organic Products to Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - J T Amaro; A F Bueno; A F Pomari-Fernandes; P M O J Neves (Neotropical Entomology, 2015)

Community structure of resting egg banks and concordance patterns between dormant and active zooplankters in tropical lakes - Jayme M. Santangelo; Paloma M. Lopes; Monalisa O. Nascimento; Ana Paula C. Fernandes; Sandra Bartole; Marcos P. Figueiredo-Barros; João J. F. Leal; Francisco A. Esteves; Vinicius F. Farjalla; Claudia C. Bonecker; Reinaldo L. Bozelli (Hydrobiologia, 2015)

Polymorphism in apoptotic BAX (-248G>A) gene but not in anti-apoptotic BCL2 (-938C>A) gene and its protein and mRNA expression are associated with cervical intraepithelial neoplasia - Ana Teresa G. Fernandes; Natália P. Rocha; Elena Vendrame; Fabio Russomano; Beatriz J. Grinsztejn; Ruth K. Friedman; Amanda C. Pinto; Evandro M. Klumb; Elyzabeth Avvad; Jacyara Macedo; Otoniel Martínez-Maza; Maria da Gloria Bonecini-Almeida (Apoptosis, 2015)

Removal of p-Nitrophenol from Aqueous Solution Using Brazilian Peat: Kinetic and Thermodynamic Studies - S. Jaerger; A. dos Santos; A. N. Fernandes; C. A. P. Almeida (Water, Air, & Soil Pollution, 2015)

An appraisal of biological responses and network of environmental interactions in non-mining and mining impacted coastal waters - Christabelle E. G. Fernandes; Ashish Malik; V. K. Jineesh; Sheryl O. Fernandes; Anindita Das; Sunita S. Pandey; Geeta Kanolkar; P. P. Sujith; Dhillan M. Velip; Shagufta Shaikh; Samita Helekar; Maria Judith Gonsalves; et al. (Environmental Science and Pollution Research, 2015)

Phosphorus Uptake, Use Efficiency, and Response of Potato Cultivars to Phosphorus Levels - Rogério P. Soratto; Cristiane Pilon; Adalton M. Fernandes; Letícia A. Moreno (Potato Research, 2015)

Microsatellite loci in the oceanic whitetip shark and cross-species amplification using pyrosequencing technology - N. J. Mendes; V. P. Cruz; Fernando Fernandes Mendonça; B. G. Pardo; R. Coelho; F. Y. Ashikaga; S. M. Camargo; P. Martínez; C. Oliveira; M. N. Santos; F. Foresti (Conservation Genetics Resources, 2015)

$$\dot{V}{\text{O}}_{ 2}$$ V ˙ O 2 kinetics and metabolic contributions during full and upper body extreme swimming intensity - J. Ribeiro; P. Figueiredo; A. Sousa; J. Monteiro; J. Pelarigo; J. P. Vilas-Boas; H. M. Toussaint; R. F. Fernandes (European Journal of Applied Physiology, 2015)

Spatiotemporal variation in life history traits of three small fishes in streams of south‐eastern Brazil - L. S. Lourenço; U. P. Souza; I. M. Fernandes; M. Petrere (Fisheries Management and Ecology, 2015)
Each species has a reproductive strategy that is adapted to the intensity and predictability of spatial and temporal variations in local environmental conditions. This study sets out to evaluate the temporal and spatial variations in some life history traits, including maturation time and length at first maturity, of three small fish species from streams of south‐eastern Brazil. Environmental factors and fishes were sampled in streams across four sub‐basins during twelve months and were measured for both traits. Statistical models indicated both spatial and temporal differences in maturation time for all species. This variation was related to a different combination of environmental factors for each species. Finally, length at first maturity exhibited spatial variation for all species. The results suggest that all species have the ability to alter life history parameters, and this may be a factor contributing to their persistence in each habitat.

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

Selective protection of the cerebellum against intracerebroventricular LPS is mediated by local melatonin synthesis - Luciana Pinato; Sanseray da Silveira Cruz-Machado; Daiane G. Franco; Leila M. G. Campos; Erika Cecon; Pedro A. C. M. Fernandes; Jackson C. Bittencourt; Regina P. Markus (Brain Structure and Function, 2015)

Computational analysis of polyethylene wear in anatomical and reverse shoulder prostheses - C. Quental; J. Folgado; P. R. Fernandes; J. Monteiro (Medical & Biological Engineering & Computing, 2015)

Soil Phosphorus Increases Dry Matter and Nutrient Accumulation and Allocation in Potato Cultivars - Adalton M. Fernandes; Rogério P. Soratto; Cristiane Pilon (American Journal of Potato Research, 2015)

Improved sea level record over the satellite altimetry era (1993–2010) from the Climate Change Initiative project - M. Ablain; A. Cazenave; G. Larnicol; M. Balmaseda; P. Cipollini; Y. Faugère; M. J. Fernandes; O. Henry; J. A. Johannessen; P. Knudsen; O. Andersen; J. Legeais; et al. (Ocean Science, 2015)
Sea level is one of the 50 Essential Climate Variables (ECVs) listed by the Global Climate Observing System (GCOS) in climate change monitoring. In the past two decades, sea level has been routinely measured from space using satellite altimetry techniques. In order to address a number of important scientific questions such as "Is sea level rise accelerating?", "Can we close the sea level budget?", "What are the causes of the regional and interannual variability?", "Can we already detect the anthropogenic forcing signature and separate it from the internal/natural climate variability?", and "What are the coastal impacts of sea level rise?", the accuracy of altimetry-based sea level records at global and regional scales needs to be significantly improved. For example, the global mean and regional sea level trend uncertainty should become better than 0.3 and 0.5 mm year−1, respectively (currently 0.6 and 1–2 mm year−1). Similarly, interannual global mean sea level variations (currently uncertain to 2–3 mm) need to be monitored with better accuracy. In this paper, we present various data improvements achieved within the European Space Agency (ESA) Climate Change Initiative (ESA CCI) project on "Sea Level" during its first phase (2010–2013), using multi-mission satellite altimetry data over the 1993–2010 time span. In a first step, using a new processing system with dedicated algorithms and adapted data processing strategies, an improved set of sea level products has been produced. The main improvements include: reduction of orbit errors and wet/dry atmospheric correction errors, reduction of instrumental drifts and bias, intercalibration biases, intercalibration between missions and combination of the different sea level data sets, and an improvement of the reference mean sea surface. We also present preliminary independent validations of the SL_cci products, based on tide gauges comparison and a sea level budget closure approach, as well as comparisons with ocean reanalyses and climate model outputs.

Rivastigmine but not vardenafil reverses cannabis-induced impairment of verbal memory in healthy humans - E. L. Theunissen; P. Heckman; E. B. de Sousa Fernandes Perna; K. P. C. Kuypers; A. Sambeth; A. Blokland; J. Prickaerts; S. W. Toennes; J. G. Ramaekers (Psychopharmacology, 2015)

Scaling up experimental ocean acidification and warming research: from individuals to the ecosystem - Ana M. Queirós; José A. Fernandes; Sarah Faulwetter; Joana Nunes; Samuel P. S. Rastrick; Nova Mieszkowska; Yuri Artioli; Andrew Yool; Piero Calosi; Christos Arvanitidis; Helen S. Findlay; Manuel Barange; et al. (Global Change Biology, 2015)
Understanding long‐term, ecosystem‐level impacts of climate change is challenging because experimental research frequently focuses on short‐term, individual‐level impacts in isolation. We address this shortcoming first through an interdisciplinary ensemble of novel experimental techniques to investigate the impacts of 14‐month exposure to ocean acidification and warming ( OAW ) on the physiology, activity, predatory behaviour and susceptibility to predation of an important marine gastropod ( Nucella lapillus ). We simultaneously estimated the potential impacts of these global drivers on N. lapillus population dynamics and dispersal parameters. We then used these data to parameterize a dynamic bioclimatic envelope model, to investigate the consequences of OAW on the distribution of the species in the wider NE Atlantic region by 2100. The model accounts also for changes in the distribution of resources, suitable habitat and environment simulated by finely resolved biogeochemical models, under three IPCC global emissions scenarios. The experiments showed that temperature had the greatest impact on individual‐level responses, while acidification had a similarly important role in the mediation of predatory behaviour and susceptibility to predators. Changes in Nucella predatory behaviour appeared to serve as a strategy to mitigate individual‐level impacts of acidification, but the development of this response may be limited in the presence of predators. The model projected significant large‐scale changes in the distribution of Nucella by the year 2100 that were exacerbated by rising greenhouse gas emissions. These changes were spatially heterogeneous, as the degree of impact of OAW on the combination of responses considered by the model varied depending on local‐environmental conditions and resource availability. Such changes in macro‐scale distributions cannot be predicted by investigating individual‐level impacts in isolation, or by considering climate stressors separately. Scaling up the results of experimental climate change research requires approaches that account for long‐term, multiscale responses to multiple stressors, in an ecosystem context.

A novel downscaling approach to predict plant invasions and improve local conservation actions - Rui F. Fernandes; Joana R. Vicente; Damien Georges; Paulo Alves; Wilfried Thuiller; João P. Honrado (Biological Invasions, 2014)

Rasgrf2 controls noradrenergic involvement in the acute and subchronic effects of alcohol in the brain - Alanna C. Easton; Andrea Rotter; Anbarasu Lourdusamy; Sylvane Desrivières; Alberto Fernández-Medarde; Teresa Biermann; Cathy Fernandes; Eugenio Santos; Johannes Kornhuber; Gunter Schumann; Christian P. Müller (Psychopharmacology, 2014)

Tropical Plant Extracts as Sources of Grain-Protectant Compounds Against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - L P Ribeiro; J D Vendramim; M S Andrade; K U Bicalho; M F G F Silva; P C Vieira; J B Fernandes (Neotropical Entomology, 2014)

In vitro and ex vivo models indicate that the molecular clock in fast skeletal muscle of Atlantic cod is not autonomous - Carlo C. Lazado; Hiruni P. S. Kumaratunga; Kazue Nagasawa; Igor Babiak; Christopher Marlowe A. Caipang; Jorge M. O. Fernandes (Molecular Biology Reports, 2014)

Molecular Markers EST-SSRs for Genotype-Phenotype Association in Sugarcane - Valdir Diola; M. H. P. Barbosa; C. F. M. Veiga; E. C. Fernandes (Sugar Tech, 2014)

Observed seasonal and intraseasonal variability of the East India Coastal Current on the continental slope - A Mukherjee; D Shankar; V Fernando; P Amol; S G Aparna; R Fernandes; G S Michael; S T Khalap; N P Satelkar; Y Agarvadekar; M G Gaonkar; A P Tari; et al. (Journal of Earth System Science, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Electrochemical removal of synthetic textile dyes from aqueous solutions using Ti/Pt anode: role of dye structure - Cynthia K. C. Araújo; Gustavo R. Oliveira; Nedja S. Fernandes; Carmem L. P. S. Zanta; Suely Souza Leal Castro; Djalma R. da Silva; Carlos A. Martínez-Huitle (Environmental Science and Pollution Research, 2014)

Observed intraseasonal and seasonal variability of the West India Coastal Current on the continental slope - P Amol; D Shankar; V Fernando; A Mukherjee; S G Aparna; R Fernandes; G S Michael; S T Khalap; N P Satelkar; Y Agarvadekar; M G Gaonkar; A P Tari; et al. (Journal of Earth System Science, 2014)

Rearing temperature affects Senegalese sole (Solea senegalensis) larvae protein metabolic capacity - Catarina Campos; M. Filipa Castanheira; Sofia Engrola; Luísa M. P. Valente; Jorge M. O. Fernandes; Luís E. C. Conceição (Fish Physiology and Biochemistry, 2013)

Maytenus obtusifolia Mart. (Celastraceae): a tropical woody species in a transitional evolutionary stage of the gynodioecy–dioecy pathway - Cristine R. Benevides; Isabella V. N. Haddad; Natália P. Barreira; Ana Tereza de A. Rodarte; Leonardo Galetto; Lygia Dolores R. de Santiago-Fernandes; Heloisa A. de Lima (Plant Systematics and Evolution, 2013)

Garcinia brasiliensis: insights into reproductive phenology and sexual system in a Neotropical environment - D. O. Leal; C. R. Benevides; R. C. P. Silva; L. D. R. Santiago-Fernandes; B. Sá-Haiad; H. A. Lima (Plant Systematics and Evolution, 2013)

A visual survey technique for deep‐water fishes: estimating anglerfish Lophius spp. abundance in closed areas a - F. D. McIntyre; N. Collie; M. Stewart; L. Scala; P. G. Fernandes (Journal of Fish Biology, 2013)
A visual survey technique was employed to estimate the abundance and distribution of anglerfish Lophius spp. in areas where destructive sampling methods, such as trawling, are unacceptable. To enable visual surveying at depths of over 300 m, a deep towed vehicle was developed equipped with video, lights and other sensors and was towed at speeds of up to 1·5 m s −1 and altitudes of up to 10 m (from the seabed) to survey large areas of the seabed around the Rockall Bank in the north‐west Atlantic Ocean. The system allowed for areas up to 125 000 m 2 to be surveyed, a substantial area comparable to that surveyed by demersal‐trawl sampling. Lophius spp. densities ranged from 15 to 736 fish km −2 ; these are comparable to estimated Lophius spp. densities determined by trawl surveys in adjacent areas. Estimates of Lophius spp. abundance in the closed areas ranged between 99 855 and 176 887 for the time series considered (2007–2011).

Evaluation of Paracoccidioides brasiliensis Infection by gp 43 Intradermal Test in Rural Settlements in Central-West Brazil - Ana Paula da C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Anamaria M. M. Paniago (Mycopathologia, 2013)

Plant functional types and traits as biodiversity indicators for tropical forests: two biogeographically separated case studies including birds, mammals and termites - Andrew N. Gillison; David E. Bignell; Kenneth R. W. Brewer; Erick C. M. Fernandes; David T. Jones; Douglas Sheil; Peter H. May; Allan D. Watt; Reginaldo Constantino; Eduardo G. Couto; Kurniatun Hairiah; Paul Jepson; et al. (Biodiversity and Conservation, 2013)

Effects of local and regional factors on the fish assemblage structure in Meridional Amazonian streams - Izaias M. Fernandes; Luzia S. Lourenço; Rafaela P. Ota; Milena M. M. Moreira; Cláudio H. Zawadzki (Environmental Biology of Fishes, 2013)

Identification of a novel subtype of feline immunodeficiency virus in a population of naturally infected felines in the Brazilian Federal District - T. G. Marçola; C. P. C. Gomes; P. A. Silva; G. R. Fernandes; G. R. Paludo; R. W. Pereira (Virus Genes, 2013)

Fungal endophytes from cactus Cereus jamacaru in Brazilian tropical dry forest: a first study - Jadson D. P. Bezerra; Marília G. S. Santos; Renan N. Barbosa; Virgínia M. Svedese; Débora M. M. Lima; Maria José S. Fernandes; Bruno S. Gomes; Laura M. Paiva; Jarcilene S. Almeida-Cortez; Cristina M. Souza-Motta (Symbiosis, 2013)

Botanical characterization of Petiveria alliacea L. from Rio de Janeiro, Brazil: Systematic and functional implications - B. O. Soares; D. C. Fernandes; L. Cantelmo; L. P. Rocha; J. A. Pettinelli; A. G. Christo; M. G. P. Coelho; R. F. Gagliardi (Plant Biosystems, 2013)

Fast error analysis of continuous GNSS observations with missing data - M. S. Bos; R. M. S. Fernandes; S. D. P. Williams; L. Bastos (Journal of Geodesy, 2013)

Sorption of Cadmium in Some Soil Amendments for In Situ Recovery of Contaminated Soils - M. D. Carrillo Zenteno; R. C. A. de Freitas; R. B. A. Fernandes; M. P. F. Fontes; C. P. Jordão (Water, Air, & Soil Pollution, 2013)

Starch determination in Chlorella vulgaris—a comparison between acid and enzymatic methods - Bruno Fernandes; Giuliano Dragone; Ana P. Abreu; Pedro Geada; José Teixeira; António Vicente (Journal of Applied Phycology, 2012)

An operational model for the West Iberian coast: products and services - M. Mateus; G. Riflet; P. Chambel; L. Fernandes; R. Fernandes; M. Juliano; F. Campuzano; H. de Pablo; R. Neves (Ocean Science, 2012)
This paper presents the structure and application of a regional scale operational modelling tool for the West Iberian coast, and discusses its potential for products and services for both scientific and coastal management activities. The forecasting suite includes nested hydrodynamic models forced with up-to-date meteorological forecast data and large-scale model results. The present status of the system and its recent upgrades are reviewed, offering a general description of the main components of the system: the forcing data, the circulation model, the model outputs and the validation methodology of model results. Seasonal differences in temperature, salinity and current velocity fields are illustrated and show satisfactory reproduction of the top and deep layer thermodynamics. The system provides boundary forcing for a number of local-scale model applications via downscaling of the solution and enables potential products and services from which civil society will benefit.

−1131T>C and SW19 polymorphisms in APOA5 gene and lipid levels in type 2 diabetic patients - Mirelle O. Sóter; Karina B. Gomes; Ana P. Fernandes; Maria das G. Carvalho; Poliana S. Pinheiro; Adriana A. Bosco; Daniel D. R. Silva; Marinez O. Sousa (Molecular Biology Reports, 2012)

Richness of endophytic fungi isolated from Opuntia ficus-indica Mill. (Cactaceae) and preliminary screening for enzyme production - J. D. P. Bezerra; M. G. S. Santos; V. M. Svedese; D. M. M. Lima; M. J. S. Fernandes; L. M. Paiva; C. M. Souza-Motta (World Journal of Microbiology and Biotechnology, 2012)

Mixed response in bacterial and biochemical variables to simulated sand mining in placer-rich beach sediments, Ratnagiri, West coast of India - Christabelle E. G. Fernandes; Anindita Das; B. N. Nath; Daphne G. Faria; P. A. Loka Bharathi (Environmental Monitoring and Assessment, 2012)

Further characterization of tomato-infecting begomoviruses in Brazil - Leonardo C. Albuquerque; Arvind Varsani; Fernanda R. Fernandes; Bruna Pinheiro; Darren P. Martin; Paulo de Tarso Oliveira Ferreira; Thaís Oliveira Lemos; Alice K. Inoue-Nagata (Archives of Virology, 2012)

Hypericum sp.: essential oil composition and biological activities - Ana P. Guedes; G. Franklin; Manuel Fernandes-Ferreira (Phytochemistry Reviews, 2012)

Erratum to: Pivotal role of the strictly conserved aromatic residue F15 in the cytochrome c 7 family - Joana M. Dantas; Leonor Morgado; Yuri Y. Londer; Ana P. Fernandes; Ricardo O. Louro; P. Raj Pokkuluri; Marianne Schiffer; Carlos A. Salgueiro (JBIC Journal of Biological Inorganic Chemistry, 2012)

Pivotal role of the strictly conserved aromatic residue F15 in the cytochrome c 7 family - Joana M. Dantas; Leonor Morgado; Yuri Y. Londer; Ana P. Fernandes; Ricardo O. Louro; P. Raj Pokkuluri; Marianne Schiffer; Carlos A. Salgueiro (JBIC Journal of Biological Inorganic Chemistry, 2012)

HFE, MTHFR, and FGFR4 genes polymorphisms and breast cancer in Brazilian women - Anna P. Batschauer; Nathalia G. Cruz; Vanessa C. Oliveira; Fernanda F. Coelho; Izabela R. Santos; Michelle T. Alves; Ana P. Fernandes; Maria G. Carvalho; Karina B. Gomes (Molecular and Cellular Biochemistry, 2011)

Effects of composition of labile organic matter on biogenic production of methane in the coastal sediments of the Arabian Sea - Maria-Judith Gonsalves; Christabelle E. G. Fernandes; Sheryl Oliveira Fernandes; David L. Kirchman; P. A. Loka Bharathi (Environmental Monitoring and Assessment, 2011)

Apolipoprotein A5-1131T>C polymorphism, but not APOE genotypes, increases susceptibility for dyslipidemia in children and adolescents - D. D. V. Brito; A. P. Fernandes; K. B. Gomes; F. F. Coelho; N. G. Cruz; A. P. Sabino; J. E. Cardoso; P. P. Figueiredo-Filho; R. Diamante; C. R. Norton; M. O. Sousa (Molecular Biology Reports, 2011)

Mitochondrion-rich cells distribution, Na+/K+-ATPase activity and gill morphometry of the Amazonian freshwater stingrays (Chondrichthyes: Potamotrygonidae) - Wallice P. Duncan; Naara F. Silva; Marisa N. Fernandes (Fish Physiology and Biochemistry, 2011)

Ultrastructural changes during early infection of Vigna unguiculata and Phaseolus vulgaris leaves by Xanthomonas axonopodis pv. phaseoli and an unexpected association between chloroplast and mitochondrion - André de O. Carvalho; Maura Da Cunha; Rosana Rodrigues; Cláudia P. Sudré; Izabela S. Santos; Kátia V. S. Fernandes; Guilherme R. Rabelo; Valdirene M. Gomes (Acta Physiologiae Plantarum, 2011)

In vitro transference and molecular characterization of bla TEM genes in bacteria isolated from Portuguese ready-to-eat foods - P. Amador; R. Fernandes; I. Duarte; L. Brito; C. Prudêncio (World Journal of Microbiology and Biotechnology, 2011)

Magnetite Content Evaluation on Magnetic Drug Delivery Systems by Spectrophotometry: A Technical Note - Érica Lira Silva-Freitas; Juliana Fernandes Carvalho; Thales R. F. Pontes; Rafael P. Araújo-Neto; Artur Silva Carriço; Eryvaldo Socrates Tabosa Egito (AAPS PharmSciTech, 2011)

Isolation of Cellulolytic Fungi from Waste of Castor (Ricinus communis L.) - Polyanna N. Herculano; D. M. M. Lima; M. J. S. Fernandes; R. P. Neves; C. M. Souza-Motta; A. L. F. Porto (Current Microbiology, 2011)

Bioreactor System Using Noninvasive Imaging and Mechanical Stretch for Biomaterial Screening - Jonathan A. Kluge; Gary G. Leisk; Robyn D. Cardwell; Alexander P. Fernandes; Michael House; Andrew Ward; A. Luis Dorfmann; David L. Kaplan (Annals of Biomedical Engineering, 2011)

Geochemistry of Palaeoproterozoic volcanic rocks of the Iricoumé Group, Pitinga Mining District, Amazonian craton, Brazil - Ronaldo Pierosan; Evandro Fernandes de Lima; Lauro Valentin Stoll Nardi; Artur Cesar Bastos Neto; Cristina P. de Campos; Kym Jarvis; José Maximino Tadeu Miras Ferron; Mauricio Prado (International Geology Review, 2011)

Cobalt Immobilization by Manganese Oxidizing Bacteria from the Indian Ridge System - Runa Antony; P. P. Sujith; Sheryl Oliveira Fernandes; Pankaj Verma; V. D. Khedekar; P. A. Loka Bharathi (Current Microbiology, 2011)

Nitrate levels modulate denitrification activity in tropical mangrove sediments (Goa, India) - Sheryl Oliveira Fernandes; P. A. Loka Bharathi (Environmental Monitoring and Assessment, 2011)

Floral structure and palynology of Podostemum weddellianum (Podostemaceae: Malpighiales) - B. de Sá-Haiad; C. A. Torres; V. H. R. de Abreu; M. R. Gonçalves; C. B. F. Mendonça; L. D. R. de Santiago-Fernandes; C. P. Bove; V. Gonçalves-Esteves (Plant Systematics and Evolution, 2010)

Perinatal l-arginine and antioxidant supplements reduce adult blood pressure but not ameliorate the altered vascular function in spontaneously hypertensive rats - Diego B. de Queiroz; Fernanda E. Ramos-Alves; Raphaella L. Fernandes; Cíntia P. Zuzu; Glória P. Duarte; Fabiano E. Xavier (Journal of Physiology and Biochemistry, 2010)

Distribution of non-native invasive species and soil properties in proximity to paved roads and unpaved roads in a quartzitic mountainous grassland of southeastern Brazil (rupestrian fields) - Newton P. U. Barbosa; G. Wilson Fernandes; Marco A. A. Carneiro; Lélis A. C. Júnior (Biological Invasions, 2010)

Selenium in the prevention of human cancers - Mikael Björnstedt; Aristi P. Fernandes (EPMA Journal, 2010)

Isolation and characterization of 13 tetranucleotide microsatellite loci in the Stone marten (Martes foina) - Mafalda P. Basto; Mónica Rodrigues; Margarida Santos-Reis; Michael W. Bruford; Carlos A. Fernandes (Conservation Genetics Resources, 2010)

Selection of native trees for intercropping with coffee in the Atlantic Rainforest biome - Helton N. Souza; Irene M. Cardoso; José M. Fernandes; Flávia C. P. Garcia; Verônica R. Bonfim; Alvori C. Santos; Anôr F. Carvalho; Eduardo S. Mendonça (Agroforestry Systems, 2010)

Effects of tryptamine on growth, ultrastructure, and oxidative stress of cyanobacteria and microalgae cultures - C. Churro; A. S. Fernandes; E. Alverca; F. Sam-Bento; S. Paulino; V. C. Figueira; A. J. Bento; S. Prabhakar; A. M. Lobo; L. L. Martins; M. P. Mourato; P. Pereira (Hydrobiologia, 2010)

Water quality and bacteriology in an aquaculture facility equipped with a new aeration system - Sheryl O. Fernandes; Shantanu S. Kulkarni; Resha R. Shirodkar; Sheetal V. Karekar; R. Praveen Kumar; R. A. Sreepada; Christian Vogelsang; P. A. Loka Bharathi (Environmental Monitoring and Assessment, 2010)

Influence of Brazilian herbal regulations on the use and conservation of native medicinal plants - Maria G. L. Brandão; Gustavo P. Cosenza; Acácia M. Stanislau; Geraldo W. Fernandes (Environmental Monitoring and Assessment, 2010)

Liver Histopathology in Brown Trout (Salmo trutta f. fario) from the Tinhela River, Subjected to Mine Drainage from the Abandoned Jales Mine (Portugal) - J. Carrola; A. Fontaínhas-Fernandes; P. Matos; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2009)

Ants on plants: a meta-analysis of the role of ants as plant biotic defenses - Felix B. Rosumek; Fernando A. O. Silveira; Frederico de S. Neves; Newton P. de U. Barbosa; Livia Diniz; Yumi Oki; Flavia Pezzini; G. Wilson Fernandes; Tatiana Cornelissen (Oecologia, 2009)

Dual augmentation for aerobic bioremediation of MTBE and TCE pollution in heavy metal-contaminated soil - V. C. Fernandes; J. T. Albergaria; T. Oliva-Teles; C. Delerue-Matos; P. De Marco (Biodegradation, 2009)

Effects of the Papaya meleira virus on papaya latex structure and composition - Silas P. Rodrigues; Maura Da Cunha; José A. Ventura; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2009)

Fire‐related traits for plant species of the Mediterranean Basin - S. Paula; M. Arianoutsou; D. Kazanis; Ç Tavsanoglu; F. Lloret; C. Buhk; F. Ojeda; B. Luna; J. M. Moreno; A. Rodrigo; J. M. Espelta; S. Palacio; et al. (Ecology, 2009)
Plant trait information is essential for understanding plant evolution, vegetation dynamics, and vegetation responses to disturbance and management. Furthermore, in Mediterranean ecosystems, changes in fire regime may be more relevant than direct changes in climatic conditions, making the knowledge of fire‐related traits especially important. Thus the purpose of this data set was to compile the most updated and comprehensive information on fire‐related traits for vascular plant species of the Mediterranean Basin, that is, traits related to plant persistence and regeneration after fire. Data were collected from an extensive literature review and from field and experimental observations. The data source is documented for each value. Since life history traits may vary spatially or with environmental conditions, we did not aggregate them by species; i.e., traits and species are repeated in different records if they were observed by different researchers and/or in different locations. Life history traits included in the data set are: life form, resprouting ability (after fire, after clipping, or after other disturbances that remove all the aboveground biomass), resprouting bud source, heat‐stimulated germination, other germination cues, seed bank location and longevity, post‐fire seedling emergence and survival, maturity age of resprouts and saplings, and seed mass. Several traits are unknown for many species; consequently, the data set reflects the state of the knowledge on the topic. However, since the ability to resprout is a trait of paramount relevance in fire‐prone environments, it was considered a core trait in the data set, and thus species whose resprouting capacity was unknown were not included. Life form is also provided for all taxa. The structure of the database allows different levels of information (and accuracy) for each entry, and thus some traits may include different types of data (quantitative, semi‐quantitative, or categorical) from different sources. The data set is structured in 8263 records and 11 columns, obtained from 301 published and unpublished sources of information. It includes 952 taxa determined at specific or infraspecific level, which comprise 859 species, 384 genera, and 79 families. Although this is the most comprehensive data set of fire‐relevant plant traits for Mediterranean species, there is still a considerable need for observations and experiments, especially in little‐studied Mediterranean areas, such as northern Africa. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Drug discrimination and neurochemical studies in α7 null mutant mice: tests for the role of nicotinic α7 receptors in dopamine release - Davide Quarta; Christopher G. Naylor; Jacques Barik; Cathy Fernandes; Susan Wonnacott; Ian P. Stolerman (Psychopharmacology, 2009)

Ionic regulation and Na + –K + ‐ATPase activity in gills and kidney of the freshwater stingray Paratrygon aiereba living in white and blackwaters in the Amazon Basin - W. P. Duncan; O. T. F. Costa; M. L. G. Araújo; M. N. Fernandes (Journal of Fish Biology, 2009)
During low‐water period, freshwater stingray Paratrygon aiereba collected in the whitewater (WW) of the River Amazon showed higher urea content, osmolality, Na + and Cl − concentrations in plasma and perivisceral fluid than those caught in blackwater (BW) of the River Negro. Gills and kidney Na + –K + ‐ATPase activities were significantly lower in WW than in BW fish. The high level of kidney Na + –K + ‐ATPase activity in P. aiereba may minimize ion loss and generate diluted solute‐free urine in ion‐poor BW environment.

Depth‐dependent swimbladder compression in herring Clupea harengus observed using magnetic resonance imaging - S. M. M. Fässler; P. G. Fernandes; S. I. K. Semple; A. S. Brierley (Journal of Fish Biology, 2009)
Changes in swimbladder morphology in an Atlantic herring Clupea harengus with pressure were examined by magnetic resonance imaging of a dead fish in a purpose‐built pressure chamber. Swimbladder volume changed with pressure according to Boyle’s Law, but compression in the lateral aspect was greater than in the dorsal aspect. This uneven compression has a reduced effect on acoustic backscattering than symmetrical compression and would elicit less pronounced effects of depth on acoustic biomass estimates of C. harengus .

Weibull statistical analysis of granite bending strength - P. M. Amaral; J. Cruz Fernandes; L. Guerra Rosa (Rock Mechanics and Rock Engineering, 2008)

Acute Toxicity of Atrazine, Endosulfan Sulphate and Chlorpyrifos to Vibrio fischeri, Thamnocephalus platyurus and Daphnia magna, Relative to Their Concentrations in Surface Waters from the Alentejo Region of Portugal - P. Palma; V. L. Palma; R. M. Fernandes; A. M. V. M. Soares; I. R. Barbosa (Bulletin of Environmental Contamination and Toxicology, 2008)

The influence of stroke mechanics into energy cost of elite swimmers - Tiago M. Barbosa; R. J. Fernandes; K. L. Keskinen; J. P. Vilas-Boas (European Journal of Applied Physiology, 2008)

Evaluation of tests to assess the quality of mine-contaminated soils - P. Alvarenga; P. Palma; A. P. Gonçalves; R. M. Fernandes; A. de Varennes; G. Vallini; E. Duarte; A. C. Cunha-Queda (Environmental Geochemistry and Health, 2008)

Fast error analysis of continuous GPS observations - M. S. Bos; R. M. S. Fernandes; S. D. P. Williams; L. Bastos (Journal of Geodesy, 2008)

Comparing directional line sets using non-parametric statistics: a new approach for geoenvironmental applications - P. C. Fernandes da Silva; J. C. Cripps (Stochastic Environmental Research and Risk Assessment, 2008)

Copper incorporation into recombinant CotA laccase from Bacillus subtilis: characterization of fully copper loaded enzymes - Paulo Durão; Zhenjia Chen; André T. Fernandes; Peter Hildebrandt; Daniel H. Murgida; Smilja Todorovic; Manuela M. Pereira; Eduardo P. Melo; Lígia O. Martins (JBIC Journal of Biological Inorganic Chemistry, 2008)

Oxidative stress activates insulin-like growth factor I receptor protein expression, mediating cardiac hypertrophy induced by thyroxine - A. S. R. Araujo; A. T. Enzveiler; P. Schenkel; T. R. G. Fernandes; M. F. M. Ribeiro; W. A. Partata; S. Llesuy; A. Belló-Klein (Molecular and Cellular Biochemistry, 2007)

Cytochemical and ultrastructural study of anoikis and secondary necrosis in enterocytes detached in vivo - Ana do Vale; Carolina Costa-Ramos; Daniela S. P. Silva; Paula M. Macedo; Rui Fernandes; Paula Sampaio; Nuno M. S. dos Santos; Manuel T. Silva (Apoptosis, 2007)

Environmental assessment of water-courses of the Turvo Limpo River basin at the Minas Gerais State, Brazil - C. P. Jordão; P. R. S. Ribeiro; A. T. Matos; R. K. X. Bastos; R. B. A. Fernandes; R. L. F. Fontes (Environmental Monitoring and Assessment, 2007)

In vitro cytotoxicity activity on several cancer cell lines of acridone alkaloids and N -phenylethyl-benzamide derivatives from Swinglea glutinosa (Bl.) Merr. - P. A. C. Braga; D. A. P. Dos Santos; M. F. D. G. F. Da Silva; P. C. Vieira; J. B. Fernandes; P. J. Houghton; R. Fang (Natural Product Research, 2007)

Impaired performance of alpha7 nicotinic receptor knockout mice in the five-choice serial reaction time task - E. Hoyle; R. F. Genn; C. Fernandes; I. P. Stolerman (Psychopharmacology, 2006)

Amino sugars in suspended particulate matter from the Bay of Bengal during the summer monsoon of 2001 - Loreta Fernandes; Fraddry D’Souza; S. G. P. Matondkar; Narayan B. Bhosle (Journal of Earth System Science, 2006)

Perturbations of the T1 copper site in the CotA laccase from Bacillus subtilis: structural, biochemical, enzymatic and stability studies - Paulo Durão; Isabel Bento; André T. Fernandes; Eduardo P. Melo; Peter F. Lindley; Lígia O. Martins (JBIC Journal of Biological Inorganic Chemistry, 2006)

Micro-emultocrit technique: A valuable tool for determination of critical HLB value of emulsions - Janus P. F. Macedo; Leonardo L. Fernandes; Fábio R. Formiga; Michael F. Reis; Toshiyuiky Nagashima Júnior; Luiz A. L. Soares; E. Socrates T. Egito (AAPS PharmSciTech, 2006)

Ligand binding and signalling pathways of PTH receptors in sea bream (Sparus auratus) enterocytes - J. Rotllant; P. M. Guerreiro; B. Redruello; H. Fernandes; L. Apolónia; L. Anjos; A. V. M. Canario; D. M. Power (Cell and Tissue Research, 2006)

Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - A. Crespí; S. Bernardos; A. Castro; C. P. Fernandes; F. Amich (Plant Biosystems, 2005)

Manganese Oxidation by Bacterial Isolates from the Indian Ridge System - Sheryl Oliveira Fernandes; K. P. Krishnan; V. D. Khedekar; P. A. Loka Bharathi (BioMetals, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Tolerance to nicotine in mice lacking α7 nicotinic receptors - C. Naylor; D. Quarta; C. Fernandes; I. P. Stolerman (Psychopharmacology, 2005)

Cryopreservation of Robinia pseudoacacia - H Verleysen; P Fernandes; I. Snchez Pinto; E. Van Bockstaele; P Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Energy cost and intracyclic variation of the velocity of the centre of mass in butterfly stroke - Tiago M. Barbosa; K. L. Keskinen; R. Fernandes; P. Colao; A. B. Lima; J. P. Vilas-Boas (European Journal of Applied Physiology, 2005)

The costs of intersexuality: a crustacean perspective - A. T. Ford; T. F. Fernandes; P. A. Read; C. D. Robinson; I. M. Davies (Marine Biology, 2004)

Behavioral Changes in Workers of the Leaf-Cutting Ant Atta sexdens rubropilosa Induced by Chemical Components of Eucalyptus maculata Leaves - A. L. Marsaro; R. C. Souza; T. M. C. Della Lucia; J. B. Fernandes; M. F. G. F. Silva; P. C. Vieira (Journal of Chemical Ecology, 2004)

Recent Geodetic Results in the Azores Triple Junction Region - R. M. S. Fernandes; L. Bastos; B. A. C. Ambrosius; R. Noomen; S. Matheussen; P. Baptista (Pure and Applied Geophysics, 2004)

Vegetation structure descriptors regulating the presence of wild rabbit in the National Park of Peneda-Gers, Portugal - A. Monzn; P. Fernandes; N. Rodrigues (European Journal of Wildlife Research, 2004)

Calculation of the solution properties of flexible macromolecules: methods and applications - J. Garca de la Torre; H. E. Prez Snchez; A. Ortega; J. G. Hernndez; M. X. Fernandes; F. G. Daz; M. C. Lpez Martnez (European Biophysics Journal, 2003)

Distribution and genetic diversity of tomato-infecting begomoviruses in Brazil * - S. G. Ribeiro; L. P. Ambrozevcius; A. C. vila; I. C. Bezerra; R. F. Calegario; J. J. Fernandes; M. F. Lima; R. N. de Mello; H. Rocha; F. M. Zerbini (Archives of Virology, 2003)

Geochemistry of water and ground water in the Nhecolândia, Pantanal of Mato Grosso, Brazil: variability and associated processes - Laurent Barbiéro; José P. Queiroz Neto; Gilles Ciornei; Arnaldo Y. Sakamoto; Benjamin Capellari; Erminio Fernandes; Vincent Valles (Wetlands, 2002)

A comparative study of the antipyretic effects of indomethacin and dipyrone in rats - G. E. P. de Souza; R. A. Cardoso; M. C. C. Melo; A. S. C. Fabricio; V. M. S. Silva; M. Lora; A. J. De Brum-Fernandes; G. A. Rae; S. H. Ferreira; A. R. Zampronio (Inflammation Research, 2002)

Production and biomass accumulation of periphytic diatoms growing on glass slides during a 1-year cycle in a subtropical estuarine environment (Bay of Paranaguá, southern Brazil) - Frederico P. Brandini; Eduardo T. da Silva; Franciane M. Pellizzari; Alessandra L. O. Fonseca; Luciano F. Fernandes (Marine Biology, 2001)

Glucose does not activate the plasma-membrane-bound H + -ATPase but affects pmaA transcript abundance in Aspergillus nidulans - Basem M. Abdallah; Tânia Simões; Alexandra R. Fernandes; Joseph Strauss; Bernhard Seiboth; Isabel Sá-Correia; Christian P. Kubicek (Archives of Microbiology, 2000)

Wave directional spectrum from SAR imagery - A. A. Fernandes; Y. V. B. Sarma; H. B. Menon; P. Vethamony (Journal of the Indian Society of Remote Sensing, 2000)

Differential expression of proliferative, cytoskeletal, and adhesive proteins during postnatal development of the hamster submandibular gland - Rui P. Fernandes; Douglas A. Cotanche; Kelley Lennon-Hopkins; Fatih Erkan; A. Sue Menko; M. A. Kukuruzinska (Histochemistry and Cell Biology, 1999)

Activation of the H + -ATPase in the plasma membrane of cells of Saccharomyces cerevisiae grown under mild copper stress - Alexandra R. Fernandes; Francisco P. Peixoto; I. Sá-Correia (Archives of Microbiology, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Free-feeding insect herbivores along environmental gradients in Serra do Cipó: basis for a management plan - Sérvio P. Ribeiro; Marco A.A. Carneiro; G. Wilson Fernandes (Journal of Insect Conservation, 1998)

Global patterns in local number of insect galling species - Peter W. Price; G. Wilson Fernandes; Angela Christina F. Lara; Jeffrey Brawn; Hector Barrios; Mark G. Wright; Servio P. Ribeiro; Nikita Rothcliff (Journal of Biogeography, 1998)
We evaluate a three‐part hypothesis explaining why gall‐inducing insect species richness is so high in scleromorphic vegetation: (1) persistence of low nutrient status scleromorphic leaves facilitates the galling habit in warm temperate latitudes; (2) favourable colonization sites for gallers result from reduced hygrothermal stress, high phenolics in the outer cortex of the gall, and reduced carnivore and fungal attack in the gall; and (3) in more mesic sites, mortality is high due to carnivore attack and invasion of galls by fungi. Over 280 samples of local species of galling herbivorous insects from fourteen countries on all continents except Antarctica revealed a strong pattern of highest richness in warm temperate latitudes, or their altitudinal equivalents. The peak of galling species richness on the latitudinal gradient from the equator into the Arctic was between 25 to 38° N or S. Galling species were particularly diverse in sclerophyllous vegetation, which commonly had greater than twelve species per local sample. In mesic, non‐sclerophyllous vegetation types the number of galling species was lower with twelve or fewer species present. Many sites in sclerophyllous vegetation supported between thirteen and forty‐six galling species locally, including campina islands in Amazonia, cerrado savanna in central Brazil, the Sonoran Desert in Arizona and Mexico, shrubland in Israel, fynbos in South Africa and coastal scleromorphic vegetation in Australia. At the same latitude, or its elevational equivalent, galling species richness was significantly higher in relatively xeric sites when compared to riparian or otherwise mesic habitats, even when scleromorphic vegetation dominated the mesic sites. The results were consistent with the hypothesis and extend to a more general level the patterns and predictions on the biogeography of gall‐inducing insects.

Production of Fumonisins B1 and B2 by Toxinogenics Strains of Fusarium moniliforme in Corn Cultures - A. P. Peito; C. Abrantes; H. Batalha; A. M. Fernandes; I. Felgueiras (Cereal Research Communications, 1997)

The mouse homologs of RELA and MLK3 are located within a 120-kb fragment on Chromosome 19 - M. Fernandes; C. Poirier; N. J. Lassam; C. Larsson; J. -L. Guénet; P. Gaudray; G. F. Carle (Mammalian Genome, 1997)

Exposure to metallic mercury in workers in a tropical chloralkali plant evaluated through urine analysis, Rio de Janeiro, Brazil - O. Malm; C. F. Calasans; A. P. Fernandes; W. R. Bastos; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

Vicilin storage proteins inhibit yeast growth and glucose stimulated acidification of the medium by cells - V. M. Gomes; L. A. Okorokov; M. P. Sales; K. V. S. Fernandes; T. L. Rose; J. Xavier Filho (Folia Microbiologica, 1997)

Effects of zinc on copper-induced and spontaneous lipid peroxidation - P. M. Filipe; A. C. Fernandes; C. F. Manso (Biological Trace Element Research, 1995)

The agroforestry systems database at ICRAF - P. A. Oduol; P. Muraya; E. C. M. Fernandes; P. K. R. Nair; A. Oktingati; J. maghembe (Agroforestry Systems, 1988)

The agroforestry systems database at ICRAF - P. A. Oduol; P. Muraya; E. C. M. Fernandes; P. K. R. Nair; A. Oktingati; J. maghembe (Agroforestry Systems, 1988)

Multipurpose leguminous trees and shrubs for agroforestry - P. K. R. Nair; E. C. M. Fernandes; P. N. Wambugu (Agroforestry Systems, 1984)

Forest villages: an agroforestry approach to rehabilitating forest land degraded by shifting cultivation in Thailand - S. A. Boonkird; E. C. M. Fernandes; P. K. R. Nair (Agroforestry Systems, 1984)